Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 670943892 species occurrences available in GBIF matching the query: (Query is too complex. Can be viewed on the landing page) The dataset includes 670943892 records from 13197 constituent datasets: 288 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 4 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 710 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 161 records from An overlooked diversity-the Costellariidae (Gastropoda: Neogastropoda) of the Miocene Paratethys Sea. 3 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 5 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 11 records from Waldstück Bremerhagen LK Bio Kl. 12. 6 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Inventaire des mammifères du Parc de la Haute-Île (93). 48 records from Planktic foraminifera counts of sediment core RC08-49. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 162 records from Plan de gestion de la Réserve Naturelle Régionale de la Massonne - Inventaire de données. 540 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 12 records from Bannwald Burghauser Forst. 1 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin du Muséum d'Histoire Naturelle [1895- ]. 3048 records from SEWBReC Bees, Wasps and Ants (South East Wales). 53 records from Données du Comité Départemental de Protection de la Nature et de l'Environnement de Loir-et-Cher (CDPNE) - Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 366 records from UCSC Elephant Seals (aggregated per 1-degree cell). 78 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 24 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 5 records from HRC Koa Kai Marine Species Monitoring Vessel Surveys November 2010. 593 records from COA Bird Collection (Arctos). 37 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 30 records from Total foraminifera counts of multinet M33/1_MSN1029. 5 records from Benthic foraminifera and algae abundance of Hole 81-552A. 1598 records from University of Guam Insect Collection. 24 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 49 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Florent HERVOUET. 23 records from Planktic foraminifera abundance of Hole 32-310. 2 records from Artenvielfalt des "Grünen Klassenzimmers". 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 388 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 99 records from AMAPPS Southeast Aerial Cruise Fall 2016. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 698 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 104 records from UWIZM Molluscs. 807 records from MCP-Aves - Coleção de Aves. 18 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 4 records from Projet de parc éolien sur la commune d'Envronville - Données faune terrestre. 17 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 159 records from Bird specimens of Saitama Museum of Natural History. 1 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 14 records from Entomofauna de la Ecoreserva Campo Rubiales (Meta, Puerto Gaitán)- Proyecto FIBRAS. 188 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 32 records from Colección de Entomología - Curculionidae. 181 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 1020 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 2 records from Centrale Hydroélectrique de Port à l'Anglais. 20 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 25 records from Total foraminifera counts of multinet M21/4_MSN704. 56 records from Plan de gestion 2017 - 2021 du site des Coteaux du Légal (24) mené par le CEN Aquitaine - Observations ornithologiques (Indice Ponctuel d'Abondance) réalisées par Vya Natura (étude de l'avifaune nicheuse). 1 records from Bees in the UVM Zadock Thompson Zoological Collection. 1 records from NZCS Brownsberg Nature Park Monitoring. 1 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 20 records from IOV-UDO-ZOOPLANCTON-PLAYA COLORADA. 17732 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 177 records from 59 - Beau Gui Avifaune. 40 records from BIRDRACE The early birds. 1 records from RECORD Orthoptera Data. 3396 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 70 records from ONCFS Réseau Ours brun - Ours 2010 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 16 records from Sunshine Coast Council Turtle Tracking (aggregated per 1-degree cell). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 7 records from Oberservation of birds at station PS14/143 along 49° West. 20 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 182 records from 2020_biodiversity_information_specimen. 2251 records from Upper Silesian Museum, Bird Observations. 61 records from ISM Ichthyology Collection. 52 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Quentin ROME. 49 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 4 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 94 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 10 records from mabik_pr. 5 records from Artenvielfalt auf dem Schulgelände. 61 records from National Museum of Natural Science. 36 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 5850 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Alain Noël. 23 records from BIRDRACE Pfeifenten. 36 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Laurence Beauchamp. 75 records from Ladybirds of Ireland. 32 records from Collections ichtyologiques et herpétologiques (BOUM). 388 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bruno OGER. 94 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 2 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1015 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 6 records from NE Scotland fish records 1800-2010. 130 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2008. 6 records from bmhs_weatherheadshell_collection. 23599 records from Fichier communal des ongulés. 521 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 4 records from Projet éolien de Saint-Barbant - Autre faune. 10428 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 3663 records from Service National d'Observation CORAIL - Réseau de surveillance Polynesia Mana - Peuplements de poissons. 87 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 67 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 368 records from HogWatch Scotland Project - West European hedgehog records between 2019 and 2021. 3 records from Roter Berg Werdau (Leubnitz). 20 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 8551 records from University of Nebraska State Museum Birds Collection. 1538 records from University of California Santa Barbara Invertebrate Zoology Collection. 9 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 24 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Observations naturalistes d'Hervé BRUSTEL. 2147 records from Entomology Collection at the Natural History Museum of Utah. 18 records from Planktic foraminifera abundance of Hole 45-395. 2296 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 46 records from NMML Small Cetacean Aerial Survey 1997. 30 records from Hartland Nature Club Lepidoptera Collection. 44 records from ALCB - Herbário Alexandre Leal Costa. 38 records from BIRDRACE LiLaLau. 14 records from Herbarium specimens of Limoges university (LIMO). 51430 records from Fish specimens of Kagoshima University Museum. 133 records from UTEP Invertebrates (Arctos). 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Pierre DUCAMP. 7 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 51 records from CNIN/Abejas de México/Apoidea. 75 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 125 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 842 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 30 records from Total foraminifera counts of multinet M36/6_MSN1196. 3 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 4 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 2 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2600 records from MMS Seabird Ecology Study 1985. 79 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 42 records from ONCFS Réseau Ours brun - Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 12 records from Planktic foraminifera counts of sediment core V14-77. 24 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 216 records from Invasive Non-Native Species, Outer Hebrides. 10 records from Phase 2 Lowland Grassland Survey of Wales. 145 records from hymenoptera. 187 records from AFTT JAX Aerial Survey -Left side- 2014. 232 records from Naturalis Biodiversity Center (NL) - Crustacea. 22 records from Amphibian and Reptilian (KIEE-AR). 757 records from Danish Ants (Formicidae). 11 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 1460 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 331741 records from CLICNAT- Base de données naturaliste picarde - CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 31942 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 11 records from Hawksbill turtles in Torres Strait (aggregated per 1-degree cell). 96066 records from DATAVES. 295 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 99 records from The Broward College Insect Collection. 290 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 2359 records from SILENE-FAUNE-PACA - Ecosphère_2017_12_18. 20 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 57 records from Fermanagh Flora. 7712 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 19 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Anna Even. 15 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 28 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 175 records from UNCW Aerial Survey 1998-1999. 2 records from Kystfuruskoger i Tysnes og Fusa. 5 records from Regroupement d'études et inventaires - Suivi Pies-grièches. 184 records from Atlas of Bats from Continental Portugal 2013. 179 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - BIO Alas, cantos y colores. 2 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 5 records from Teich Berlin Wuhlheide. 41 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 28 records from Planktic foraminifera abundance of Hole 21-207. 2 records from AKG-Gelände (Bensheim). 19 records from Diagnostic écologique et élaboration d'une notice de gestion (prairies humides et calcaires) sur la commune de Monflanquin (47) menés entre 2017 et 2022 par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 128 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 3332 records from Fish observations delivered by "Canarias por una Costa Viva" project. 14 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 6 records from Ostracoda abundance of Hole 48-403. 5 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 595 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 15 records from Lebensraum Gesamtschule (Langerwehe). 35 records from Planktic foraminifera counts of sediment core V27-178. 9 records from Foraminifera abundance of Hole 64-481. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kathy FOOT. 198 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 285 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 1 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 20 records from Total foraminifera counts of multinet M21/2_MSN648. 91851 records from NOAA AFSC North Pacific Groundfish Observer. 1383 records from Données Association Évasion tropicale (AET) - Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 110 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 463 records from Fish (NHMK-PI). 152 records from Ferme pilote d'éoliennes flottantes de Groix & Belle-Ile et son raccordement au Réseau Public de Transport d'Electricité - Campagne d’investigations ichtyofaune – Ferme pilote de Groix & Belle-Ile. 1 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 97 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 7 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 2 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 25 records from Total foraminifera counts of multinet M21/4_MSN694. 10 records from Planktic foraminifera abundance of Hole 14-142. 400 records from Insects, Outer Hebrides. 3 records from An der Ohm, (Wettsaasen). 2 records from Philippine Mollusk Symbiont - ICBG Collection. 119 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1469 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 4 records from Reptiles de la Ecoreserva Refinería (Santander, Barrancabermeja) - Proyecto FIBRAS. 1 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 41 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 360 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 14 records from Jurica-Suchy Nature Museum at Benedictine University Fossil Specimens (Arctos). 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 12583 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 24 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 132 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Inventaire entomologique 2020 de la réserve biologique dirigée du Nord Grande Terre, Guadeloupe (ONF). 7229 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 182 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 34 records from Happywhale - Bryde's whale in South Atlantic Ocean. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 510 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 24 records from Total foraminifera counts from M35/1_MSN1065. 2394 records from Marine Turtles. 17 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 81 records from Gabon 2009-10: Pongara, Leatherback Turtles (aggregated per 1-degree cell). 30 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Suivis rapaces 2019 - Site Natura 2000 des Barthes de l'Adour. 1020 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 2011 - 2015 Coordonnées GPS Lambert 93. 20 records from Total foraminifera counts of multinet M21/2_MSN650. 207 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 104 records from Vermont Orthoptera Records from Historic Dot Maps. 423 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 30 records from Global Register of Introduced and Invasive Species - Alaska, United States. 46 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 5 records from Naturgrundstück (Eutin). 11 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 1 records from 1ère phase d'animation (2017 - 2020) des Documents d’objectifs des sites Natura 2000 FR7200665 "Coteaux calcaires de Proissans, Sainte-Nathalène et Saint-Vincent-le-Paluel", FR7200672 "Coteaux calcaires du Causse de Daglan et de la Vallée du Céou" et FR7200676 "Coteaux calcaires de Borrèze" (24) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 13893 records from Données de la plateforme régionale SINP DREAL Bourgogne - Données de l'Observatoire de la Faune de Bourgogne. 66 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 143 records from Fungi of parks, forests and reserves of New Jersey, 2018. 1 records from Plan de gestion 2017 - 2021 du site des neuf fontaines et de l'airial du Larousse (40) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 160 records from Phenological Center - Birds (Murmansk). 71 records from Hawthorne Canal Birdwatching Survey. 1 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 2409 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 2478 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 1036 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 22 records from Grassland cartography SICONA, Recorder-Lux database. 156 records from Allan Herbarium (CHR). 7124 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2138 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 18 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 148 records from CRC HRC Shore-based Surveys KB11 2013-2015. 46 records from Línea base general de hormigas para el valle medio del Magdalena - VMM. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Séverine VITRAT. 2 records from Données naturalistes d'Olivier LAURENT. 1 records from Uncultured eukaryotes Targeted Locus (Loci). 1571 records from Restauración y conservación de Isla Guadalupe. 8 records from Animation du Document d’objectifs du site Natura 2000 FR7200799 - Carrières de Castelculier (47) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 66 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 20 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 682 records from Collections of Bioclass, school #179, Moscow. 5820 records from BLM CETAP AIR Sightings. 30 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 18 records from Microbial community structure and dynamics in the oxygen minimum zone of the Northeast subarctic Pacific Ocean. 26 records from Mycology collection, Norwegian Forest and Landscape Institute. 11547 records from Mammalia (Luomus). 30705 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 8 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 49 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 54 records from UWIZM Anoles. 154 records from Pat Livermore's Fungus Records 1976 - 2000. 9 records from Macrobenthos Chukchi Sea, 1986. 6 records from Condamine Alliance. 12 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 353 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 3 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 12 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 81 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 467 records from Mesures compensatoires sur des projets de Collectivités territoriales - Données CEN L-R Compensation collectivités. 4 records from Faunal assemblage of sediment core TR149-31. 269 records from AMAPPS Northeast Aerial Cruise Summer 2010. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 4 records from données espèces - Expertise IPE 63. 346 records from Herbier Louis-Marie (QFA) - Collection de lichens. 35 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 60477 records from Inventaire des oiseaux nicheurs de France métropolitaine 2009-2012 - Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BLANC Josselyne. 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 16 records from Planktic foraminifera abundance of Hole 29-284A. 24 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 592 records from Monitoring of colonial waterfowl species (2013-2014). 5 records from Colección de Zoología Universidad Icesi: Mamíferos. 66 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 364 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 12 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 152 (N.S) n°45 (2), 2017 - Données faune. 20 records from Total foraminifera counts of multinet M21/2_MSN650. 181 records from Colecção Entomológica IIA. 4 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 3755 records from MZFC/Coleccion de Aves. 276 records from Wintering wildfowl in Portugal – 1992-1993. 19 records from Manx Wildlife Trust - Records. 21 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 1429 records from Spatial and temporal ichthyofauna community of a tropical mangrove Bay (Gazi Bay, Kenya) sampled between 1994 and 1996. 4227 records from DMNS Egg Collection (Arctos). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 107 records from Lepidopterous specimens of Yamagata Prefectural Museum. 56 records from UNCW Hatteras Aerial Survey - Right side - 2015. 1 records from Orthoptera - SMF. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 16 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (3), 2009 - Données faune. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 20 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 129071 records from Florida Keys Reef Visual Census 2014. 17 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 1 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 120 records from University of Michigan Museum of Paleontology - Vertebrates. 27 records from CNMI Sea Turtle Program satellite tracked green turtles 2011. 88 records from Compost microbe establishment and growth in agricultural soils. 1941 records from National Benthic Inventory. 4 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 38 records from BIRDRACE Die Wendehälse. 36 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 14 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 265 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 39 records from Inventaire Entomologique, E. DECAUX 1998 - Inventaire des données récoltées par Emmanuelle DECAUX et la SEL. 22 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 37 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 6 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 20 records from DSMZ Bacteria. 502 records from Ornithological observations in the Kharkiv region of Ukraine. 4678 records from CAS Entomology (ENT). 21965 records from Programme CarNET B (Cartographie Nationale des Enjeux Territorialisés de Biodiversité Remarquable) - Carnet B Lorraine. 12679 records from Naturalis Biodiversity Center (NL) - Pisces. 22 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 68 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 126 records from Myxomycetes collection of the University of Eastern Finland. 13531 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 23612 records from Seasearch Marine Surveys in England. 3 records from The Evaniidae (Hymenoptera: Evanioidea) of Turkey. 17 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 6 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 591 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 3 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 2 records from Herbarium, Natural History Museum of Utah. 20 records from Fossil Specimens of Komatsu City Museum. 94 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 16 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 25 records from Occurrence of mammalia relicts at site Geißenklösterle. 4 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 358 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Bernard Lalanne-Cassou. 37 records from PSUZC-Reptile Collection. 2 records from Planktic foraminifera counts of sediment core RC13-154. 7 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 264 records from Inventaire des papillons diurnes de Martinique - Données de collection de l'inventaire des Papillons de jour de Martinique. 274 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 37 records from Inventaires Odonatologiques de sites ENS du Pôle Nature de Vitrezay (St Sorlin de Conac) et de St Clément des baleines - Liste odonates 2 sites ENS Charente-Maritime. 1550 records from BioGIS - Mammals - SPNI. 365 records from Amphibia and Reptilia (Luomus). 7118 records from Données du Parc national des Cévennes - Inventaire et suivis d'espèces dans le Parc national des Cévennes. 9 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 285578 records from SEWBReC Birds (South East Wales). 63 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 73 records from Lepidoptera of Mordovia State Nature Reserve. 144 records from Peces de las lagunas costeras de Isla Margarita, Venezuela. 24 records from Total foraminifera counts from multinet SO119_MSN1285. 2761 records from MfN - Fossil vertebrates IV. 30 records from Dipterists Forum: Field Week 1981 (Kent). 1859 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de Corse par Canard A., Rollard C., Villepoux O.. 2000 records from Eulachon migration bottom trawl surveys. 109 records from Projet éolien - Oiseaux - Inventaire non protocolé. 1321 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 4326 records from Amphibiens et Reptiles de France (Enquête 2). 725 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 24 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 16 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Alain BERLY. 2987 records from Herps Specimens. 625 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 36 records from (Table 6) Ostracod assemblages of sediment core 9409. 125 records from Regroupement d'études et inventaires - Données opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 20 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 24 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 3 records from Elaboration du DOCOB du site Natura 2000 ’Réseau hydrographique du Midou et du Ludon’ (FR7200806) - Inventaire et regroupement de données Natura 2000. 3310 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 13 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1997. 10 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi naturaliste du Parc du Peuple de l'Herbe. 192 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 84 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 32 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 460 records from Species biodiversity transnational geo-database - IMPRECO Project. 9942 records from Données de Mammifères issues de Baznat. Midi-Pyrénées - Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 5 records from KUO Fish collections (KUO). 42 records from bmhs_butterfly_collection. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 37 records from Planktic foraminifera counts of sediment core V04-8. 28 records from checklist-of-birds-of-zomba-mountain. 182 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 131 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Loïc SALAUN. 188 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 5006 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 555 records from East Ayrshire Species Database. 5 records from Euroants. 116 records from Collection Crustacea - ZMB. 5 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 173 records from Georgia Aquarium/DomSeTCO Leatherback's of Dominica (aggregated per 1-degree cell). 81 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 30 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 189 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 33 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 33 records from Dermaptera in the icipe collection. 30 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 1002 records from The national database for marine data (MADS). 13 records from Foraminifera abundance of Hole 57-440A. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Kevin CURTIL. 58 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 321 records from Canary Islands - OAG (aggregated per 1-degree cell). 6 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 4 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 26 records from Construction du village Alzheimer à Dax (40) - Inventaire de la Faune patrimoniale. 6 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 20 records from Life Vison d'Europe et espèces associées - Données de Vison d'Europe par piège-photo, capture ou indices indirects (empreintes...). 36 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Anaelle WILLER. 2 records from Warnowufer Groß Klein. 2 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 524 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from Plan de gestion 2013 - 2018 du site du Coteau de Peymourel (24) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 9 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 230 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 30 records from Colección del Herbario de la Universidad de los Llanos. 493 records from Alterra (NL) - Entomofauna inventory in peat swamps. 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1016 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 12 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 4507 records from University of Minnesota Insect Collection. 3217 records from ARABEL - Arachnologia Belgica. 55143 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 17 records from Heinersdorfer Sumpfwiese. 15120 records from Arctic Species Trend Index (ASTI) : Marine. 15 records from Missisquoi National Wildlife Refuge Bumblebee (Bombus) Surveys. 5 records from Expertise dans le cadre d'une sollicitation liée à une étude d'impact - Données études d'impact CEN M-P. 40 records from Ohio Wesleyan University Mammal Specimens (Arctos). 7205 records from Wolli Creek Preservation Society Bird Survey. 12473 records from MLZ Bird Collection (Arctos). 64 records from Projet de transport par câble entre le Chaudron, Moufia et Bois de Nèfles - Oiseaux - inventaires. 8 records from Naturschutzgebiet Müchelholz (Mücheln). 6 records from Wiese am Waldrand (Gurtweil). 2 records from NMML Gulf of Alaska marine mammal survey 2003. 2 records from Veille écologique - Suivi des papillons de jour. 96 records from Gastropod Specimens of the Yamagata Prefectural Museum. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 39 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 186 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 32 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 7 records from Happywhale - Leatherback Sea Turtle in North Pacific Ocean. 43 records from Demande de renouvellement et d'extension d'autorisation de carrière au titre de la rubrique 2510 des ICPE - Carrière de Villemanoche (89) - Donnees biodiversite carriere Villemanoche 181210. 3 records from Culicidae of Guam. 5228 records from Herbarium Senckenbergianum (FR) - Fungi. 1712 records from National System of Protected Areas in Poland - Animals. 784 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 3 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 28 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 661 records from AMAPPS Northeast Aerial Cruise Summer 2016. 82 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 2 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 57 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 462552 records from First Bird Atlas. 1120 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 852 records from MMS Marine Mammal Survey, PNW 1989-1990. 74 records from Reptilia ZMK. 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 3 records from Diversity of Spiders from Azorean Trails. 3172 records from United Kingdom National Whale Stranding Database 1913-2008. 7292 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Christophe CHAMBOLLE. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Laurent ROUSSERIE. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 56 records from Base BOMBINA du Parc Naturel régional Lorraine - Natura 2000 Vallée de la Seille. 43 records from Inventario de Hymenóptera; parasítica en México. 7 records from MfN - Fossil Fish Collection. 46 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 386 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 40 records from Projet de carrière - Ravine du Trou - Saint-Leu (974) - Inventaires des Oiseaux. 2 records from Planktic foraminifera abundance of Hole 9-76. 22 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 5 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 214 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 25 records from BIRDRACE Nachtigallen. 3 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données de Midi-Pyrénées transmises par Pascal Peyrache.. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de THÉVENOT Jessica. 2 records from Deep Sea fishes (Chondrichthyes, Osteichthyes) in the Southwestern Colombian Caribbean. 30 records from Total foraminifera counts of multinet FCA97C_MSN1345. 7 records from Occurrence of mammalia relicts at site Biedermann. 18 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 13 records from Plan de gestion du Marais du Logit - Inventaire opportuniste Faune. 2535 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 110 records from Birds Specimens of Akita Prefectural Museum. 21 records from Planktic foraminifera counts of sediment core A15-558. 125 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2009. 5 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LE GLOANEC Vincent. 99239 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81, 1983-5. 1102 records from MSUM Ichthyology and Herpetology Collections. 632 records from Whale catches in the Southern Ocean. 41 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 1287 records from Genebank, National Institute of Agrobiological Sciences. 6 records from Plan régional d'actions en faveur des odonates (PRAO) : 4ème phase (2019 - 2020) menée par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine (Étude Leucorrhines). 11 records from River Biologists' Database (EPA). 86 records from Great Eastern Ranges - Slopes to Summit. 287 records from Tiroler Landesmuseum Ferdinandeum. 2103 records from Données de l'association Nature 18 - Données faune Nature 18 - 2017. 34 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 18 records from Mammals (GNHM-MM). 15 records from Données supplémentaires Atlas des Mammifères marins. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 25 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 5 records from Protist Diversity in the East China Sea. 8 records from Données espèces - Expertise IPE 79. 232458 records from NBIS Records to December 2016. 6 records from Rohrmeistereiplateau und angrenzendes Gebiet. 24 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 74 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 115 records from South American Antarctic Marine Biodiversity Literature. 1 records from SILENE-FAUNE-PACA - Métropole_Nice_Côte_d'Azur_2017_12_18. 1 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 13 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 1902 records from California State University, Long Beach Birds. 4 records from Ostracoda abundance of Hole 24-238. 421 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 871 records from Happywhale - Leopard seal in Southern Ocean. 282 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 5850 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 185 records from NE Scotland other invertebrate records 1800-2010. 6 records from Données opportunistes faune du Groupe d'Étude et de Protection des Oiseaux en Guyane. - Données d'observations de Mammifères marins de Guyane issues de www.faune-guyane.fr. GEPOG et LPO. 8 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 32 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 208 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Données Entomologiques A. HORELLOU 1988-2018. 18 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Foraminifera abundance of Hole 74-526A. 39 records from Iowa State University Fishes Collection. 50 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 11 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Plan de gestion 2015 - 2019 du site du Coteau de Monco (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LESSIEUR David. 14 records from Species inventories NP Öewersauer, Recorder-Lux Database. 5 records from "Schwarzwassertal" bei Pobershau. 16 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 1 records from marine metagenome Targeted Locus (Loci). 4323 records from Plan de vertebrados de la Patagonia. 192 records from Distribution of planktic foraminifera of sediment core M35003-4. 95 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Planktic foraminifera abundance of Hole 22-217. 6 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 27029 records from Activité générale du bureau d'étude BIOTOPE (1994 - 2013) - Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 8 records from Danielsberg (Mölltal, Kärnten). 9 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 2394 records from SILENE-FAUNE-PACA - LPO_PACA_2017_12_18. 6 records from Targeting a portion of central European spider diversity for permanent preservation. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 126 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 6 records from Sonidos de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 63 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae). 2 records from Fauna Species of Camiguin Island, Philippines. 1 records from Plan de gestion 2016 - 2020 du site des Landes humides de Mouguerre (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 1796 records from Denver Museum of Nature & Science - Entomology. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Marc GAGNE. 25 records from Projet du parc éolien de la Voie des Prêtres 2 - Liste de l'avifaune recensée en période de reproduction en 2010 et 2011. 474 records from Some finds of birds, mammals, amphibians and reptiles in autumn and winter 2021 - 2022 in Kharkiv region, Ukraine. 33 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 307 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 57 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 186 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 2916 records from 成龍溼地鳥類生態紀錄. 407 records from Strathclyde badger sett surveys 1996-2000. 69 records from UNCW JAX Aerial Survey -Left side- 2017. 150 records from Evaluation des MAEC - Inventaire Oiseaux sur les prairies en MAEC. 604 records from SEFSC Southeast Cetacean Aerial Survey 1992. 90104 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 2 records from Characteristics of eukaryotic plankton community in the Coastal Waters of Rongcheng by Illumina sequencing. 302 records from Spider (NSMK-SP). 1 records from OUPR - Herbário "Professor José Badini". 9513 records from National Biodiversity Data Bank. Observation records, 1900-2014. 21 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 11 records from Atlas des papillons de jour et des libellules du Languedoc-Roussillon - Données CEN L-R papillons/libellule. 2 records from Occurrence database of bryophytes and native animals of southern Chile. 25 records from Total foraminifera counts of multinet M21/4_MSN720. 1 records from VFD-H: Heidenrod: Pferdeweide Mürth. 409 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 7 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Julien PIOLAIN. 9 records from Nottekanal, Klasse 7 - 10. 28 records from Percentages of planktonic foraminifera species in sediment core V30-40. 14 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 3 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 4 records from Données espèces - Expertise IPE 69. 202 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 30 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 7 records from Sea shells of New South Wales. 28 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 32 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 493 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 2 records from Flora und Fauna im Brexbachtal. 279 records from Fauna marina de la costa vasca - Sistema de Información de la Naturaleza de Euskadi. 5 records from Herpetofauna laguna El Tinije. 46 records from Birdrace-Professorenteam-Münster. 12448 records from Ontario Breeding Bird Atlas 1981-1985. 20 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 20 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 12 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 53 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 127 records from BIOWIDE eDNA Fungi dataset. 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 1510 records from Weevil and Bark Beetle records via iRecord. 1 records from Nationalpark Harz Schul-AG Braunlage. 2178 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 204 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 26 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 8 records from Was lebt in der Brutzwiese?. 1 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 1 records from Biodiversity Surveys, South-east Arnhem Land. 3 records from Planktic foraminifera abundance of Hole 22-212. 18 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 7 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 773 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 25 records from Wichita State University Collection. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre-Alexis RAULT. 321847 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 2 records from pbzt_insect_biodiversity. 384 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Avifaune Lande sèches. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 9 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 8 records from Fossil (NSMK-FO). 1062 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 137 records from Programmes d'Atlas de la biodiversité communale (ABC) - Atlas de la Biodiversité Communale sur les communes de Montmaurin, Lespugue et Blajan - Haute-Garonne - Données du CEN MP. 370 records from South Caribbean Diversity. 29 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 17 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Mikaël PAILLET. 24 records from Total foraminifera counts of multinet M21/5_MSN731. 135 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 4737 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 48 records from Planktic foraminifera abundance of Hole 72-516F. 1423 records from UNCW Right Whale Aerial Surveys 2008. 14 records from Heteroptera collections of SW Finland. 417 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 72 records from Fungi specimens of Saitama Museum of Natural History. 1014 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2006 - 2010 Coordonnées GPS Lambert 93. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 2 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 29 records from Mollusca Collection of Saitama Museum of Natural History. 1 records from SILENE-FAUNE-PACA - BIOMEO_2017_12_18. 2 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 65 records from Planktic foraminifera abundance of Hole 72-518. 9 records from Inventaires sur le réseau Aquitaine Nature du PNR Périgord-Limousin - Inventaire sur le site de la Pierre levée. 1005 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 1447 records from Bosque Mesófilo de Montaña de México. 1049 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 3 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi Conventionnement de la commune de Chepnier. 2 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 491 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 10 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 2 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 19 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 630 records from Marine benthic dataset (version 1) commissioned by UKOOA. 74 records from European Moth Nights. 5665 records from The Dolphin Project. 43 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 108 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 10 records from Inventaire national des Crustacés Décapodes de France métropolitaine - Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 1295 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 59 records from BUND - Dassower See (Lübeck/Dassow). 1587 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur François FOURNIER. 27 records from Birds and plant species near Petushki town (Vladimir region). 155 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 2 records from Convention - Fondation d'Entreprise du Golf de Vidauban pour l'Environnement - Jeu de données convention FEGVE-SPN (numéro 2). 124 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 30 records from ONCFS Réseau Ours brun - Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 126 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 128 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1434 records from Arthur Chapman Observations. 27 records from Cuxhavener Küstenheiden. 540506 records from Hatikka.fi observations. 1287 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 4 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 35 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur JOURDE Rémi. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 3952 records from inatura - Erlebnis Naturschau Dornbirn. 9 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 493 records from Birds (NHMK-BI). 93 records from ProDelphinus Peru Leatherback Tracking Project (aggregated per 1-degree cell). 40 records from Total foraminifera counts of multinet M21/6_MSN784. 2 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 108 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 195 records from Données de Aquasearch et Dauphin Passion - Données Mammifères marins Aquasearch - Dauphin Passion. 751 records from Database of invertebrates collected in Mongolia. 1 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 338 records from Insect specimen database of Atsugi City Museum. 1 records from Bulletin d'informations de l'Association française de Lichénologie. 96 records from Nematoda of Costa Rica (INBio). 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 3 records from Ferme éolienne de Saint-Hilaire-du-Maine - Insectes patrimoniaux observés durant les expertises entomologiques en 2014. 356 records from Morphologische Daten von Puffinus creatopus. 1666 records from WTSWW Data: All Taxa (West Wales). 996 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 36 records from CRESLI marine mammal observations from whale watch cruises 2000-2019. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 4 records from "Ahrschleife bei Altenahr". 27217 records from South Australian Museum Australia provider for OZCAM. 24 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 4 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 3 records from Unter hellen Zinnen und finsteren Grotten. 92 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 1888 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 2 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 2756 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 1 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 70 records from Gomex Sperm Whale Survey 2000. 139 records from Base BOMBINA du Parc Naturel régional Lorraine - Modernisation des ZNIEFF du PnrL. 49 records from Zooplancton del estrecho de Bransfield y alrededores de Isla Elefante, verano austral 2019-2020, durante la VI Expedición Científica de Colombia en la Antártica. 6 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 2 records from Occurrence of mammalia relicts at site Niederlehme. 87 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Grand Voyeux - Suivis scientifiques. 5 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 49 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 897 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 4200 records from Tasmanian Museum and Art Gallery provider for OZCAM. 189 records from TTRS Mammals. 45 records from Occurrence of mammalia relicts at site Veternica. 54 records from Mushroom (KIDR-MR). 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 2 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 18 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 498 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2003 records from Chrysomelidae beetle data from iRecord. 29 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 8 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 4 records from Faunal assemblage of sediment core TR149-32. 1022 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 7 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 19 records from Mica - Muskrat, Raccoon and Coypu occurrences collected by ITAW in Germany. 12 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 3 records from Schulgelände Lise Meitner Realschule (Paderborn). 41 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 45 records from Birdrace-SpeedBirder-Zwickauer_Land. 29 records from Birdrace-Die_Vogelscheuchen-Herford. 13188 records from Suivi Temporel des Rhopalocères de France (STERF). 198 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 10 records from Australian Museum Ichthyology - 2012 Inscription Point. 30 records from Total foraminifera counts of multinet POS247/2_MSN1386. 846 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 40 records from Projet BiodiverCité - Données opportunistes de Frédéric Revers récoltées lors des prospections terrains. 4316 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from Inventaires et suivis effectués sur les retenues collinaires de l'Institution Adour - Inventaire sur la retenue collinaire de Renung. 12 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 22 records from Glasgow Museums BRC: Chrysomelidae. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Projet de parc éolien en mer des îles d'Yeu et de Noirmoutier - demande de dérogation espèces protégées - Mammifères marins GT - Inventaire non protocolé. 30 records from Total foraminifera counts of multinet FCA97C_MSN1339. 35 records from Aves de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 28 records from Bryde’s whales off eastern Venezuela - Vessel 1978-1979. 7 records from USAC Mammals Collection. 818 records from Collection ornithologique A. Maës. 1274 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 27 records from Mammal specimens of Komatsu City Museum. 1 records from Urban Barcode Project - Fungi. 36 records from 2018_nsmk_biodiversity_pi. 2 records from Örtzemündung (Stedden). 51 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 600003 records from Eremaea. 1075 records from Marine Offshore Seabed Survey data held by JNCC. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 65 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Occurrence of mammalia relicts at site Sütto_6. 398 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 61 records from Monitoreo de aves rapaces y no rapaces en una plantación de paltos y almendros, comuna de Paine, Región Metropolitana de Santiago, Chile.. 1 records from A Giant Honey Bee from the Middle Miocene of Japan (Hymenoptera: Apidae). 5 records from Swiss National Diplopoda Databank. 1 records from Freies Projekt Speichersdorf - Region Oberfranken. 109 records from BIRDRACE Gätkes Erben. 103 records from Distribution of seabirds at sea in the Gulf of Carpentaria, Australia (1990-1991). 92 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 2260 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1786 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 30 records from Total foraminifera counts of multinet M21/1_MSN608. 20 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 5 records from Appui technique et scientifique aux réserves naturelles (nationales et régionales) - Données ANA - CEN Ariège sur la RNR du massif de Saint-Barthélémy. 35 records from Birdrace_Gätkes_Schergen-Helgoland. 32 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 78 records from Avifauna asociada a la parcela de investigación de la estación Tutunendo, Quibdó, Chocó. 2020. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 78 records from Galathea II, Danish Deep Sea Expedition 1950-52. 8 records from NCSM Non-molluscan Invertebrates Collection. 114 records from KUO Coleoptera collections (KUO). 3 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 13 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 17 records from North Carolina Rehabilitated Sea Turtle Monitoring Project (aggregated per 1-degree cell). 570 records from Bird Monitoring 2017, Meise Botanic Garden. 124 records from Colecção Entomológica do Museu de História Natural de Maputo. 202 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 2 records from Craigellachie NNR invertebrate records compiled from SNH files. 6 records from Elaboration des DOCOB des sites Natura 2000 ‘Plateau d’Argentine’ (FR7200810) en 2009 et ‘Réseau hydrographique de la haute-Dronne’ (FR7200809) en 2010 - Inventaire et suivi Entomologique de Desmond KIME. 9 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 6 records from imr_mareano_rpsledge. 15 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 835 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 1037 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 116 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 11 records from Données LIFE + DESMAN CEN MP. 59 records from Cayman Islands 2004: Loggerhead & Green Turtles (aggregated per 1-degree cell). 27 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 37 records from Gulf Turtle Tracking Project 2011 (aggregated per 1-degree cell). 24 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 7 records from Abundance of benthos infauna at station GIK23055-1. 27 records from Atlas de la Biodiversité Communales sur la Communauté de Commune de Montesquieu - Données faune opportuniste récoltées en marge des protocoles Amphibien & Reptiles. 13 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 18 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 369 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 263 records from Gunma Museum of Natural History, Fungi Specimen. 1 records from Juvenile loggerhead use of the Gulf Stream off Cape Hatteras, NC (aggregated per 1-degree cell). 654 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 1 records from Kirchenforst. 6 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 25 records from Percentages of planktonic foraminifera species in sediment core V22-38. 2 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 3464 records from Atlas des oiseaux nicheurs de France réalisés par carte IGN50 - Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 237 records from DUML vessel-based line transect surveys for proposed Onslow Bay USWTR site 2007-2010. 84 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 30 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 13 records from Inventaire en continu de la ZNIEFF 'Pechs De Bouyssou Et De Vitrac' - 720020098 - Pechs de Bouyssou et de Vitrac - Inventaires Oiseaux IPA. 83 records from Caracterización de Fauna para el plan de Etnodesarrollo de Bahía Cupica, Chocó. 184475 records from PIROP Northwest Atlantic 1965-1992. 153 records from Happywhale - Southern Right Whale in South Atlantic Ocean. 182 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 37 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée de 2013 à 2017. 2 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 21 records from Plan de gestion 2013 - 2018 du Lac de La Prade (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 48222 records from UWFC Ichthyology Collection. 3 records from Etude d'aménagement foncier lié à la desserte du CHNDS - Inventaire de Lépidoptères et des Odonates. 1036 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Tourterelle des bois 1996 - 2000 Coordonnées GPS Lambert 93. 146 records from Mycological Collection of Osaka Museum of Natural History. 4 records from Auburn University Museum of Natural History Invertebrates. 69 records from UNCW JAX Aerial Survey - Right side - 2016. 1 records from Mamíferos laguna El Tinije. 1033 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 15 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Cedric DEVILLEGER. 28 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 177 records from Densidad poblacional de la Pava caucana, el Mono aullador y tres especies asociadas, para el Santuario de Fauna y Flora Otún Quimbaya en los años 2013 a 2016. 3337 records from CUMV Fish Collection. 112 records from MUST, Insecta. 54224 records from Données ONF faune-flore-fonge. 1 records from Observations occasionnelles de taxons par les agents de la Fédération (hors inventaires scientifiques) - Inventaire opportunistes Faune. 39 records from Collection entomologique Pierre Lachiver. 2 records from Deutsche Schule Budapest. 59 records from Regroupement d'études et d'inventaires - Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 3 records from Occurrence of mammalia relicts at site Trebacki krs. 1 records from Notice de gestion 2019 - 2023 de la bande de servitude de l'artère Girland (40) de Teréga mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 394 records from Ferme éolienne de Mauprévoir - Données Mauprévoir - oiseaux. 3725 records from University of Tennessee Fungal Herbarium. 3727 records from University of Michigan Museum of Zoology, Division of Mollusks. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 3 records from Setaphyes elenae sp. nov., a new species of mud dragon (Kinorhyncha: Allomalorhagida) from Skagerrak (north-eastern Atlantic Ocean). 2 records from Occurrence of mammalia relicts at site Siebenlinden 3. 30 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 1 records from Happywhale - Melon-headed Whale in South Pacific Ocean. 157 records from Données acquises par le Conservatoire botanique national du Bassin parisien et son réseau (bénévoles, associations, autres structures professionnelles) - Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 287 records from Inventaires et suivis sites compensation contournement sur la commune de DAX - Données opportunistes. 4 records from Type Specimen Database of Museum and Institute of Zoology PAS. 701 records from DASSH Data Archive Centre Academic Surveys. 227 records from SWFSC Marine Mammal Survey, CalCurCEAS 2014, Cruise 1647. 40 records from Occurrence of mammalia relicts at site Roc de Combe. 3 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 24 records from Expedición ornitológica en el municipio de Barbacoas (Nariño) - BIO Alas, cantos y colores. 67 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 2 records from Exkursion Ebertsheimer/Grünstädter Berg. 4649 records from University of Florida Invertebrate Paleontology. 39 records from Review, cladistic analysis and biogeography of Nezara Amyot & Serville (Hemiptera: Pentatomidae). 3 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 7931 records from Données Faune Base SIRFF - FNE Centre-Val de Loire - Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 212 records from SIM-Fungal records compiled by Joan Montón. 27112 records from Western Australian Museum provider for OZCAM. 1 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 8 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 203 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 7402 records from NRW Regional Data: South East Wales Non-sensitive species. 47 records from Marine Turtle Conservation Project 2012-2013 (aggregated per 1-degree cell). 49 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 108 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joana PERRODIN. 1 records from Waldstück am Schullandheim Bad Bederkesa. 30 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 584 records from Osteology collections of World Museum, National Museums Liverpool. 128 records from M. Gollop Collection. 162 records from Naturalis Biodiversity Center (NL) - Diptera. 41 records from BIRDRACE Bon(n)apartemöwen. 3059 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 103 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay hiver 2017. 2103 records from Mutualisation des données naturalistes pour le rapportage Natura2000 en 2017 - Synthèse 10x10km des espèces de la Directive Oiseaux recensée par le Groupe Ornithologique des Deux-Sèvres de 2013 à 2017. 4 records from Projet éolien - Insectes - Inventaire non protocolé. 57 records from Occurrence of mammalia relicts at site Raj Cave. 196 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 2 records from Planktic foraminifera abundance of Hole 27-260. 3096 records from Arizona State University Hasbrouck Insect Collection. 282 records from Collection Strepsiptera SMF. 2 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 488 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 247 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 43 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 18 records from Plan régional d'actions en faveur des odonates (PRAO) : 3ème phase (2017 - 2018) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées lors de journées de prospections animées par le CEN Aquitaine. 3 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3 records from Happywhale - Adelie Penguin in Southern Ocean. 2 records from Amtsrain Apolda-Zottelstedt. 104 records from MoJ BioBlitz August 2018. 1002 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 1 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from Plan de gestion 2019 - 2023 de la station botanique du Normandin (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from Plan de gestion 2013 - 2017 du site de la Butte de la Lot (33) mené par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Joël BRIED. 10 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 24 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 206 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 309 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 6 records from Dorfrand Mauderode. 39 records from SuLaMa reptile survey I 2012. 50 records from Shrews of Poland. 10 records from Morphological systematics of kingsnakes, Lampropeltis getula complex (Serpentes: Colubridae), in the eastern United States. 2032 records from K-State Museum of Entomological and Prairie Arthropod Research. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 102143 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 10 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 8239 records from Collection Pisces SMF. 5554 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 16 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1515 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 56 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 3 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 264 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 30 records from Total foraminifera counts from M35/1_MSN1051. 1415 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 9 records from Artenvielfalt auf den Elbwiesen (Dessau). 28 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 317 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 30 records from Total foraminifera counts of multinet M21/1_MSN606. 25 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 141 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 71782 records from Estonian Nature Observations Database. 1914 records from Botanical Museum, Copenhagen, Mycology Herbarium. 99 records from Birds (NMNO-BI). 1420 records from NCSM Mammalogy Collection. 9 records from Nivå Bay species list, Zealand, Denmark. 17 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 756 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 5448 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 8066 records from Fife Nature Records Centre combined dataset. 81 records from CHAS Botany Collection (Arctos). 30 records from Total foraminifera counts of multinet M21/1_MSN604. 66 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Naturschutzgebiet Lochbusch-Königswiesen. 4 records from Plan de gestion 2017 - 2021 du site des Landes humides de Mazerolles (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 92 records from BIRDRACE Niederlausitz-Team. 2 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - L'Amateur de Papillons. 9 records from Planktic foraminifera abundance of Hole 18-173. 16 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Damien TROQUEREAU. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 35 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 531 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 66 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 101 records from TRAS LA RUTA DE LAS TORTUGAS GOLFINAS EN LOS CABOS, BCS 2009-2018 !! (aggregated per 1-degree cell). 33 records from SILENE-FAUNE-PACA - CG04_2017_12_18. 99 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 243 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 2 records from A survey of small mammals in the Volta Region of Ghana with comments on zoogeography and conservation. 19 records from Observations naturalistes de la réserve naturelle nationale des prés salés d'Arès et de Lège-Cap Ferret - Plan de gestion 2016-2020 - Inventaire et suivi Faune - Protocole Wetlands International. 32 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 14 records from Vogelstimmenführung durch den Tiergarten. 2 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 7 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 30 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 472 records from Tetrápodos de Uruguay. 64 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 181 records from Bird collections of Åbo Akademi. 37 records from 2019_nsmk_mm_20200324. 25 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 43 records from Two new species of Petalophthalmus and Ipirophthalmus (Crustacea: Mysida: Petalophthalmidae), from New Zealand. 854 records from University of Kentucky Insect Collection. 1275 records from mabik_iv. 27 records from Atlas des Orthoptères et Mantides de France métropolitaine. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Bourdin Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 44 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 20143 records from UAM Bird Collection (Arctos). 9 records from Projet d'extension de la carrière de Le Blanc, Queyrac - Données brutes de biodiversité - Le Blanc, Queyrac. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 165255 records from Dry Tortugas Reef Visual Census 2014. 1 records from Ostracoda abundance of Hole 48-406. 64 records from SILENE-FAUNE-PACA - GEOECOLINK_2017_12_18. 62 records from UTEP Herpetology Osteology (Arctos). 12 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 101 records from Virginia Aquarium and US NAVY Sea Turtle Research Project (aggregated per 1-degree cell). 4295 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 27 records from kznm-entomology-collection. 3 records from Plan de gestion 2017 - 2021 du verger de Villebramar (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 23 records from Stadtpark Herzberg (Elster). 2705 records from TTRS Ornithology. 237 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 300 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 691 records from Black grouse national surveys. 52 records from Southern Maine Community College Gulf of Maine Invertebrate Data. 11 records from Bacterial diversity and community composition in grassland and forest soils of the German Biodiversity Exploratories. 3 records from Ocean crust Targeted Locus (Loci). 33 records from Planktic foraminifera abundance of Hole 80-549A. 17 records from Plan de gestion 2009 - 2013 du site de l’Étang de Chourroumillas (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 981 records from Museu Paraense Emílio Goeldi - Diptera Collection. 369 records from NEFSC Aerial Survey - Summer 1998. 465 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Julien BARITEAUD. 1 records from Marine waters Raw sequence reads. 2292 records from Invertebrate Zoology Division, Yale Peabody Museum. 3783 records from Merseyside BioBank Active Naturalists (unverified). 120 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 2105 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 47 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V23-82. 2036 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 1035 records from Swiss National Vespoidea Databank. 12 records from Planktic foraminifera counts of sediment core RC17-69. 144 records from Données des tortues marines d'Ebodjé. 2 records from CHAS Ichthyology Collection (Arctos). 384 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2019. 1 records from Nachtinsekten am Muldenufer. 200 records from The lefteye flounder family Bothidae (Order Pleuronectiformes) of Taiwan. 32 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Luc Berger. 37 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 51066 records from Israel Nature and Parks Authority. 1 records from Élaboration de la 1ère notice de gestion de la bande de servitude de l'artère Girland (40) de TIGF - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1710 records from Colección de muestras biológicas del Centro Oceanográfico de Canarias. 52 records from Micro-moths distribution for Dumfries and Galloway. 128 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de JACQUET Claire. 13 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 295 records from NEFSC Aerial Survey - Experimental 2002. 1 records from Pottundkopp. 2 records from Nine new species of Agromyzidae from North Carolina, USA, with new host and distribution records for additional species. 13 records from New species of Crella (Pytheas) Topsent, 1890 and Crellomima Rezvoi, 1925 (Crellidae, Poecilosclerida, Demospongiae) from Chilean shallow and Argentinean deep waters, with a synthesis on the known phylogenetic relationships of crellid sponges. 782 records from Catálogo de insectos de la colección del Centro de Entomología. 73 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 450 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 48 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (2), 2008 - Données faune. 13384 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1888 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 170 records from IFO Filamentous Fungi. 1 records from DAYO: Invasive Alien Reptiles in the Philippines. 41 records from Collecte permanente de données naturalistes sur la base de donnée participative en ligne de Vienne Nature (Fnat) - Synthèse 10x10km de la faune sauvage de la Directive Habitats-Faune-Flore recensée par l'association Vienne Nature de 2013 à 2017. 142 records from Mollusca specimens of Okinawa Prefectural Museum & Art Museum. 1479 records from MPM Herpetology. 4 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 139 records from Aves del Distrito de Páramos en los departamentos de Nariño-Putumayo. 2 records from Fairchild Tropical Botanic Garden (FTG). 122 records from Woodmeadow Invertebrate Survey 2017. 40 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 20 records from Antarctic Jellyfish. 30 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 32 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Audrey SAVOURE-SOUBELET. 20668 records from National Trust Species Records. 21666 records from Australian National Wildlife Collection provider for OZCAM. 526 records from Crispin S. Guppy Collection. 19 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Emmanuel ICARDO. 13 records from Projet de centrale solaire de Lyreco. 14 records from NHM, Heteroptera. 152 records from USWTR JAX Aerial Survey -Left side- 2010-2011. 1 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 24 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 22 records from FERME ÉOLIENNE DE BLANZAY - Avifaune Blanzay migpré 2016. 2042 records from Lund University Biological Museum - Insect collections Inventory. 67280 records from Australian Museum provider for OZCAM. 1300 records from Inventaires et suivis faune - Inventaire et suivi mammifères issues de pièges photographiques. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Thomas MARTINEAU. 11324983 records from Observation.org, Nature data from around the World. 1387 records from Données d'oiseaux. 28 records from iran-marine-ray-finnedfishes-1963-70. 2547 records from Mammal records for Dumfries and Galloway. 61 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Jérôme Fuhrer. 14 records from Occurrence of mammalia relicts at site Fohlenhaus-Höhlen. 1652 records from Estación Biológica Doñana - CSIC, Aves. 2 records from Cytheroid ostracods (Crustacea) from South Korea, with description of a new species. 9 records from checklist_data_for_thambani_fr_bird_list. 1 records from Occurrence of mammalia relicts at site Barova Cave. 11 records from Queens University Belfast Marine Research Data. 127 records from Projet de port de plaisance de Brétignolles sur Mer - Oiseaux - inventaire non protocolé. 84 records from Inventaires du site Natura 2000 des Marais du Haut Médoc - Inventaire naturaliste Faune. 30 records from BIRDRACE SchrägeVögel. 1614 records from NYSM Mammals. 2 records from iSpot (2008-2010): Shieldbugs & allied species. 9 records from Inventaire en continu de la ZNIEFF 'Forêt du Verdus' - 720012953 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 422 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 41 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1944 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 62 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 8267 records from WADFW PSAMP W1993. 19 records from Happywhale - White-beaked Dolphin in Arctic Ocean. 16 records from University of Algarve and ICNB Cetacean Sightings 1999. 25 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Annales de la Société entomologique de France [1832- ]. 552 records from Hymenoptera specimen database of Kyushu University. 13 records from Kastikka Literature Sources. 1 records from Plan de gestion 2012 - 2016 du site des tourbières de Mées (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 1 records from The Myriapoda Collection of the National Museum of Nature and Science. 13478 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 49 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 86 records from Elaboration du DOCOB du site Natura 2000 ‘Haute Cize’ (FR7212015) - Inventaire avifaune. 5457341 records from iNaturalist Research-grade Observations. 465 records from SEFSC GoMMAPPS 2018 Fall Aerial Survey. 1 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 18 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1 records from Planktic foraminifera abundance of Hole 84-567A. 33 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 2 records from Abundance of benthos infauna at station PS1240-1. 874 records from Mediterranean seabird surveys 99/00/02. 611 records from Données du Parc National de la Guadeloupe - Données du Râle gris sur le territoire de la Guadeloupe. 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de CARR David. 1 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 332 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 290 records from Regroupement d'études et inventaires - Collecte données faune Simethis 2014-2019. 616 records from Musée Vert ornithology collection. 319 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine - Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 210 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 4150 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 44 records from BIRDRACE Griffin Wood Warblers. 13 records from Données espèces -expertise IQE 3. 89 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 1 records from Planktic foraminifera abundance of Hole 94-611B. 82 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 348 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 193 records from Collection Berlie. 11 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Arnaud Bak. 489 records from Derek Lott Coleoptera Dataset. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 55 records from UNCW JAX Aerial Survey -Right side- 2017. 725 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2 records from Planktic foraminifera counts of sediment core V28-128. 29 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 1 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 4607 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 106 records from Likona Invertebrates. 26 records from Ferme éolienne d'Arnac sur dourdou - Avifaune. 19 records from SuLaMa reptile survey 2013. 718 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 57 records from Fish (NSMK-PI). 103 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 1 records from DBRC Hemiptera species records 1969 to 2015. 1 records from BB-Biodiversität a. 412 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 9153 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 23 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 71 records from Mesures compensatoires autoroutes - Données mesures compensatoires ASF - ex région M-P. 102 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 72 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 275 records from Cumbria Non Native Invasive Species. 27 records from Regroupement d'études et inventaires - Inventaire et suivi de la faune écrasée. 72 records from nsmk_mm_2019. 1 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 25 records from Mollusc collection Natuurmuseum Brabant, Tilburg. 13 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 7 records from Benthic foraminifera and algae abundance of Hole 81-554A. 20 records from DAR AVH data. 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 11 records from Happywhale - Commerson's Dolphin in South Atlantic Ocean. 6 records from Programmes d'étude et de conservation de populations d'espèces particulières (hors PNA et PRA) - Données CEN M-P espèces. 81 records from England Non Native Species records 1965 to 2017. 21 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Claire BETBEDER. 43 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 4 records from DBL_Life. 18 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 70 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 635 records from Océanopolis mammifères marins en Bretagne 1993-2015. 365 records from BLS Rare and Threatened Lichen Records: England. 123 records from Animation technique des sites Natura 2000 ‘Barthes de l'Adour’ - Animation des Docobs des barthes de l'Adour. 11 records from Gronau - auf der Suche nach dem Neunauge. 3 records from Fungal diversity in Sanya mangrove sediments, China. 30 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 107 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 703 records from Eden Arthropod Azores Database. 3 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 2 records from Faunal assemblage of sediment core GS7603-8. 44 records from Thrips (Thysanoptera) in Norway. 2 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Emilien HENRY. 17 records from Entdeckertour am Muldestausee 1/05. 53 records from Mammalian Specimens of the Yamagata Prefectural Museum. 16 records from Bird specimens of Ryukyu University Museum (Fujukan). 439 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 8 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 22 records from SILENE-FAUNE-PACA - BIOTOPE_2017_12_18. 36 records from BIRDRACE Diesmal sehen wir mehr. 27 records from Weevils of Poland. 49 records from Arachnida of Costa Rica (INBio). 1 records from Animation du Document d’objectifs du site Natura 2000 FR7200666 - Vallées des Beunes (24) menée par le CEN Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 194 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 136 records from Ross A. Layberry, Collection. 1 records from Atlas communaux de la biodiversité du Parc Naturel Régional des Landes de Gascogne 2014-2020 - Inventaire de la flore du PNRLG 2016 (Gironde). 4 records from Streuobstwiese Stedar 2008. 612 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 7477 records from Canadian Museum of Nature Fish Collection. 63 records from JPB - Herbário Lauro Pires Xavier. 26 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 24 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 5330 records from BioGIS - Mammals - INPA database. 642 records from Records of birds and mammals from nature reserve "Koncha-Zaspa" in literature resources authored by Mykola Charlemagne. 1 records from Mollusques continentaux de France - Données naturalistes de l'inventaire malacologique pour l’élaboration de deux dossiers de création de Réserve naturelle régionale (RNR) - Sites des Terrils n° 11 et 12 du Bois des Dames (Bruay-la-Buissière) et Ex-sablière de Chocques. 803 records from Atlas de la biodiversité de Bordeaux Métropole 2015 - Recensement des oiseaux hivernants 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 22 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 1998. 4058 records from SHARK - National zooplankton monitoring in Sweden since 1979. 30 records from Fungal 18S Ribosomal RNA (SSU) RefSeq Targeted Loci Project. 73 records from Seguimiento y control científico de las capturas de Cerambyx cerdo en montes públicos de Mallorca. 4 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 6 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 25 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de BEC Joël. 3167 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 5 records from BD de la plateforme partagée pour la diffusion des données naturalistes de Haute-Normandie - Observation des mammifères sur le territoire de la Métropole Rouen Normandie. 93 records from Chronicle of Nature - Phenology of Birds of Visimsky Nature Biosphere Reserve. 3 records from Projet de parc éolien de Keranna (22) - Inventaire des mammifères terrestres pour le projet éolien de Keranna (22). 33 records from Tag der Artenvielfalt in Heidelberg. 15938 records from Birds ringed by Revtangen Bird Observatory 1936-2018, Southwest Norway. 129 records from Censo de aves en el Parque Nacional Natural Macuira para el periodo 2011 y 2013. 22 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste HAYON Bruno provenant de la base de donnée du SINP Île-de-France CETTIA. 53 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Diagnostic des Espaces Naturels Sensibles des Yvelines. 43 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 13 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 528118991 records from EOD – eBird Observation Dataset. 5 records from HRC Kaula Vessel-Based Monitoring Surveys June 2011. 21514 records from Atlas des oiseaux nicheurs de France réalisés par carte IGN50 - Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification certaine. 14063 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 40 records from Total foraminifera counts of multinet M21/6_MSN787. 242 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 1 records from Vascular plant collections of the Botanical Museum, University of Oulu (OULU). 19 records from Überall ist Wunderland. 430 records from INNS Data: All Taxa (West Wales). 3260 records from The Taiwan Roadkill Observation Network Data Set.. 221 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 24 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Ingénieurs écologues GEREA. 519 records from Registros de fauna mediante fototrampeo en Caño Cristales, La Macarena, Meta. 14 records from sediment metagenome Metagenome. 9 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Marie-France LECCIA. 147 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 530 records from USGS Alaska Science Center Polar Bear Maternal Dens. 592 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Records of the Wine Microorganism Culture Collection. 31 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 3539 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 228 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 452 records from Aves de la cuenca media del río Bogotá. 8 records from Cabo Verde (aggregated per 1-degree cell). 152 records from Fossil Birds. 2682 records from TNHC Herpetology Collection. 19 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 157 records from Some finds of birds, mammals, insects, amphibians and reptiles in February 2018 in Assam, West Bengal, Bihar, Delhi and Uttar Pradesh (India). 2 records from Foraminifera abundance of Hole 48-406. 259 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 42033 records from Tasmanian Natural Values Atlas. 48322 records from Macaulay Library Audio and Video Collection. 220 records from Museu Darder de Banyoles. 8 records from Occurrence of mammalia relicts at site Kugelsteinhöhle II. 53 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2001. 32 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 166 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Monsieur VANDROMME Denis. 117 records from Geochemistry and sedimentology on core POS200/10_6-2. 5 records from Colección de moldes endocraneanos del CENPAT. 1150 records from Roadkill data (ANF), Recorder-Lux database. 2403 records from SIO Marine Bird and Mammal Survey 2003. 37 records from Study on plankton at the port of Ostend in 1965. 6 records from Priest Pot species list, Cumbria, Britain. 25 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 3650 records from KUO Bird collections (KUO). 4 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 9 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 2530 records from The Brown University Foraminiferal Data Base (BFD). 41 records from (Table 7) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-873B. 255 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Océane ROQUINARC'H. 5 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 386 records from Monitoreo y uso del hábitat de aves neárticas y neotropicales asociados a ambientes acuáticos litorales en el municipio de Tomatlán, Jalisco, México. 91 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 8 records from Flora y Fauna asociada a servicios ecosistémicos de polinización y zoocoria para 10 remanentes de bosque seco tropical en el Valle del Cauca. 5 records from Pilzlehrwald. 242632 records from International Barcode of Life project (iBOL). 15 records from LBV 100 - Artenvielfalt am Rothsee. 7 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Xavier BONNET. 2728 records from Lepidoptera Eastern Fennoscandia (Luomus) (LEPFEN). 97365 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 1 records from Japan Collection of Microorganisms(Basidio). 1936 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 3 records from Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean. 309 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de LATTUGA ronan. 35 records from BIRDRACE Avinauten. 463 records from Some finds of flora and fauna in Kharkiv region. 218 records from Données Ligue de protection des oiseaux de Touraine - Données 2016 de la Ligue de Protection des Oiseaux de Touraine. 526 records from Lichen field notes, Oslo (O). 988 records from Collection Mollusca SMF. 24 records from Total foraminifera counts of multinet M6/7_MSN100. 568 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Benoit MARTHA. 20 records from Total foraminifera counts of multinet M21/4_MSN707. 61 records from Avifauna presente en el resguardo indígena de Arquía, municipio de Unguía-Chocó. 2020. 9484 records from Données du Parc national des Pyrénées - Observations occasionnelles Parc national des Pyrénées. 14 records from données opportunistes générales Environat - Inventaire de données. 6 records from Foraminifera abundance of Hole 22-215. 1 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 2 records from Supporting Sea Turtle Survival at Queens Beach Bowen, Australia. (aggregated per 1-degree cell). 3 records from Diversity of beetles associated with watermelon crops Citrullus lanatus (Thunb.) Mats. in the region of Ouargla (southern Algeria). 2 records from Microlaimus capitatus sp. n. and Dichromadora simplex Timm, 1961 (Nematoda, Chromadorea) from the coast of Vietnam. 10514 records from Bird survey of Budai salt pans in Taiwan. 28 records from HRC Ground-based Surveys Aug 20 2013. 708 records from Bumblebees, cuckoobees and butterflies in southern Poland. 9 records from Planktic foraminifera abundance of Hole 26-250. 2 records from Happywhale - Southern Elephant Seal in South Pacific Ocean. 5332 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 10820 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 100 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 28 records from Percentages of planktonic foraminifera species in sediment core V29-144. 57 records from Distribution of benthic foraminifera on sediment core sediment core PS1290-4. 131 records from Royal BC Museum - Herpetology Collection. 1 records from North Sea plastic incubation and reference communities, raw sequence reads. 20 records from Planktic foraminifera abundance of Hole 23-219. 1 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 18 records from Total foraminifera counts of multinet M26/1_MSN845. 7410 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 80 records from Biodiversidad asociada al proyecto Parque Solar Fotovoltaico Tepuy. 24 records from Percentages of planktonic foraminifera species in sediment core V15-168. 595 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 1 records from Mammalia (JNHM-MM). 1 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 44 records from Biodiversidad de los Ecosistemas Mesofóticos de la Isla de San Andrés. 3 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 1019 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Faisan commun 2008 - 2012 Coordonnées GPS Lambert 93. 168 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 31 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 69 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 5 records from Inventario herpetofaunístico del noroeste de Hidalgo. 18 records from WildesMoor bei Schwabstedt. 69 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 95 records from ZooplanktonBeaufortSeaNOGAP2. 7 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 610 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1623. 2 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Vestland, Troms and Finnmark, Norway (2019). 12 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 185 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 24 records from Albury Wodonga Nature Map. 1 records from Système d'Information sur la Nature et les Paysages d'Ile de France - étude entomologique de la ZSC du Bois de Vaires. 115 records from Regroupement d'études et d'inventaires - Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 17 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 16 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 4317 records from Waterbird counts, Luomus dataset. 2 records from Inventaires et suivis sites "Espaces Naturels Sensibles" gérés par le Conseil Départemental des Landes - Inventaire "Espaces Naturels Sensibles" des saligues, (BORDÈRES-CAZÈRES-RENUNG). 5 records from Plan de gestion 2014 - 2018 de la Réserve Naturelle Régionale des carrières de Tercis-les-Bains (40) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 8 records from Planktic foraminifera abundance of Hole 94-611. 157 records from FBIP: SeaKeys - iziko_cartilaginous_fish. 1 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 171 records from Kherson State University herbarium (KHER), Department of Botany. 6 records from Total foraminifera counts of trap L3_92_45. 399 records from Inventaire des longicornes des Antilles - Inventaire des Coléoptères Longicornes des Antilles françaises. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 259326 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 16 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 160 records from SILENE-FAUNE-PACA - Département_du_Var_2017_12_18. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 24 records from Total foraminifera counts of trap L2_92_A42. 1 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 129 records from Vertebrados registrados durante el muestreo de tigrillos melánicos en el Valle del Cauca. 30 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 2 records from Wildlife Observations Bardon Hill 31.5.09. 13 records from Projet de parc solaire Figanieres - Oiseaux - inventaire non protocolé. 66 records from Carrière calcaire de Chateaupanne (Mauges-sur-Loire) - modification des conditions d'exploitation - renouvellement de l’autorisation - inventaires 2004-2014 pour étude d'impact carrière. 36 records from BIRDRACE OAG Neuwerk. 2 records from Two axiidean ghost shrimps (Crustacea: Decapoda) from India, Guyanacaris keralam sp. nov. (Axiidae) and Paragourretia galathea (K. Sakai, 2017) (Ctenochelidae). 3 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 2 records from Planktic foraminifera counts of sediment core V26-124. 1 records from Selz (Ingelheim am Rhein). 1563 records from SPC CoFish Fish Observations Nauru 2005. 287 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 1 records from A synoptic review of the family Dendronotidae (Mollusca: Nudibranchia): a multilevel organismal diversity approach. 3808 records from pins. 2 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 29 records from tree climbing bryophytes & lichens at tree base and crown with traits. 1678 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 34 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Laurent PONCET. 29 records from Mammal specimens of Natural History Museum, Kishiwada City. 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Kévin LE FALHER. 47 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 1802 records from UWBM Mammalogy Collection (Arctos). 583 records from Royal Ontario Museum Fungarium (TRTC). 15 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 80 records from SILENE-FAUNE-PACA - Butterfly_conservation_2017_12_18. 2286 records from Mesures compensatoires A65 - CDC Biodiversité - Inventaires faune. 2 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 5 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3 records from Düne am Ulvenberg (Darmstadt). 1 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Céline DELTORT. 9263 records from Mammals housed at MHNG, Geneva. 87 records from HRC CRC Small Vessel-Based Monitoring Surveys October-November 2011. 299 records from Löydös Open Invasive Species Observations. 1216 records from Mammal osteology MZS. 7 records from Grillhütte Wettsaasen, Wiese, Hecken. 16 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste VAN DEN BRINK Sylvie provenant de la base de donnée du SINP Île-de-France CETTIA. 60 records from Planktic foraminifera abundance of Hole 15-148. 24 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 7 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 8 records from Mollusca specimens of Kuroshio Biological Research Foundation. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - données bibliographiques diverses (non araignées). 84 records from AMAPPS Northeast Aerial Cruise Fall 2012. 12 records from UNM Earth Sciences Collection (Arctos). 2511 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 80 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 88 records from Inventaire des invertébrés marins benthiques et des algues de la Guadeloupe : expédition Karubenthos 2012 - Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 87 records from Caracterización biológica en la Serranía de San Lucas 2015. 64 records from Expertise IQE - Laimont 2018 - Données espèces - IQE Laimont 2018. 408 records from Bird specimens of Komatsu City Museum. 24 records from Total foraminifera counts of multinet M21/5_MSN728. 1 records from Projet de parc solaire Figanieres - Mammifères - Inventaire non protocolé. 38 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 3 records from Geotraces Raw sequence reads. 10 records from Données espèces - Expertise IPE 123. 4 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 2144 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 65 records from AMAPPS Northeast Aerial Cruise Spring 2012. 123 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 182 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 59 records from BIRDRACE Rheinische Wasserrallen. 95 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Régulière du Loup en 2004. 292 records from Abundance and biomass of zooplankton collected in front of the Danube Delta in May and September 1979. 17 records from Cetacean sightings off Turkey 2006-2011. 146 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de David HAPPE. 30 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 297 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 41 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données coléoptères de l'Association des Entomologistes de Picardie. 1 records from Curculionidae of Guam. 56 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 24 records from Total foraminifera counts from multinet M31/2_MSN890. 134 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 134 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 25 records from CNAN/Araneae. 178 records from Coleoptera collection of Uunio Saalas. 28 records from AMAPPS Northeast Aerial Cruise Spring 2014. 16841 records from Observations Regelink Ecology and Landscape. 156 records from Oskarshamn herbarium (OHN). 8 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 5 records from Michael Barkla's Observations. 1954 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica Tapachula). 36 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 27 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 14602 records from Données du CEN Picardie concernant la Faune, la Flore et la Fonge - Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 1 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 132 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 15 records from Planktic foraminifera counts of sediment core RC14-7. 1631 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 65 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste delzons olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 142 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 21 records from Chronicle of Nature - Phenology of Mammals of Tigirek State Nature Reserve. 225 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Paul LECHAPT. 404 records from Projet de parc éolien de la Forge - Données biodiversité Parc éolien de la Forge. 2 records from Metagenome from mudbank Area,Alappuzha Kerala India. 1321 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 53 records from SILENE-FAUNE-PACA - Eco-Stratégie_2017_12_18. 2 records from Fauna y flora en las cercanías del gasoducto que alimenta la mina de Ferroníquel Cerro Matoso S.A.. 31 records from Guinea-Bissau Herpetological Collection - IICT. 66 records from e-Valley, le plus grand parc e-logistique d'Europe - Oiseaux - Inventaire non standardisé. 278 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Comptage Wetlands en Essonne. 20 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 37 records from Projet de parc éolien Le Clos Neuf (22) - Données naturalistes du projet éolien de Clos Neuf (22). 292 records from Aves en fincas ganaderas sostenibles del Meta. 203 records from Camera trapping bird data. 26 records from Planktic foraminifera counts of sediment core V27-47. 7796 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes opportunistes de Philippe Legay. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 3 records from Happywhale - Steller Sea Lion in North Pacific Ocean. 13 records from Citas de mapache (Procyon lotor) en Bizkaia - Sistema de Información de la Naturaleza de Euskadi. 175 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 18 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 19 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Geai des chênes 2007 - 2011 Coordonnées GPS Lambert 93. 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 32 records from Cape Cod Sea Turtle Release 2007 (aggregated per 1-degree cell). 56 records from Modern foraminifera in the New Zealand EEZ. 15 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 2 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 3077 records from SPC CoFish Fish Observations Palau 2007. 14 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 43582 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 23 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 1 records from Planktic foraminifera abundance of Hole 28-265. 8 records from CLICNAT- Base de données naturaliste picarde - Signalements mammifères marins échoués (réellement ou juste posés), Réseau National Echouage. 1781 records from Bird collection Natuurmuseum Brabant, Tilburg. 1737 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 1 records from VMNH SVDM Invertebrate Paleontology. 42 records from Etat des lieux des suivis effectués dans le cadre de la LGV SEA - Suivi de la zone humide de Sainte Soline. 262 records from Arachnida and Myriapoda (Luomus). 5355 records from Natural England Marine Monitoring surveys. 20 records from Range table from benthic foraminifers in ODP Hole 139-857A. 340 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 7 records from Ground Beetle Recording Scheme - data verified via iRecord. 254 records from ATCC Fungi Collection Catalog. 4 records from Two new species of Geodiidae (Porifera, Demospongiae, Astrophorina) from the Emperor Seamounts, North Pacific Ocean. 467 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 16 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 5 records from Parc éolien d'Argillières - ornithologie hivernage. 133 records from Vertebrate specimens of Iwate Prefectural Museum. 36 records from Coleoptera Collection. 154 records from Зимние маршрутные учеты в природном парке «Нумто» (Ханты-Мансийский Автономный Округ). 417 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 141 records from Kangawalla Bird Sightings. 432 records from Gabon 2008-09: Mayumba & Pongara, Leatherback Turtles (aggregated per 1-degree cell). 3 records from Collection of Animal Cell Culture. 23 records from ONCFS Réseau Ours brun - Ours 2016 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 8 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 50 records from Classic localities of terrestrial Mollusca from the Western Balkans. 9 records from Importancia del Parque Estatal Cerro de la Tortuga para la conservación de los mamíferos del estado de Morelos, México. 427 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 435 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 3 records from Chronicle of Nature - Phenology of Mushrooms of FGBU National Park Kenozersky. 36 records from SILENE-FAUNE-PACA - DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 5 records from Waldwandel in Monschau-Mützenich-Boverei. 9564 records from Welsh Invertebrate Database (WID). 57 records from Bibliographie de la faune, la flore et la fonge de France métropolitaine et outre-mer - Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 197 records from Opération d'aménagement Vallée Créative - Bordeaux Métropole - Inventaire Faune. 4240 records from Regroupement d'études et inventaires de la Réserve Naturelle de l'Etang des Landes - FR3600158 - Ensemble des données. 123 records from Évaluation et préservation de la biodiversité dans les anciennes carrières de Charente-Maritime - Inventaire Faune. 60 records from Long-Term Monitoring Network Vegetation Quadrats. 36 records from Benthic foraminifera abundance of Hole 56-435. 17 records from Inventaire Rhopalocère 2008 du PNRLG - Inventaire et suivi Rhopalocères. 27 records from Parc Eolien Les 7 Domaines - Inventaire des oiseaux migrateurs en 2013 et 2014. 226 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Pierre FRAPA. 4 records from Observations naturalistes indépendantes d'origine privée partagées sur la base de données Kollect Nouvelle-Aquitaine - Observations faunistiques de Vincent LABOUREL. 2 records from Collection Crustacea ZMG. 5 records from Naturpark Kottenforst-Ville 16.6.09. 1 records from Fish specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 55 records from Planktic foraminifera abundance of Hole 15-154A. 14 records from Marine metagenomes from the bioGEOTRACES project. 6 records from Study of the biotic environment in the Sluice Dock in relation to oyster farming between 1960 and 1964. 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 9 records from Natur aus zweiter Hand am Muldestausee. 7 records from Fauna de Chilí-Barragán bajo el Convenio Interadmisnitrativo No 0018 celebrado entre CVC-INCIVA. 6 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Julien ROBAK. 31 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 93 records from Inventaire des coléoptères saproxyliques de France métropolitaine - Observations et collection de Coléoptères d'Alain Sadorge. 3323 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 30 records from Total foraminifera counts of multinet M42/3_MSN1368. 24 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 160 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 131 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1588 records from Données Association Évasion tropicale (AET) - Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 2192 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 44 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 4 records from 2020_nsmk_knam_biodiversity_mr_80. 101 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 24 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 24 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 2661 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 6 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2 records from SILENE-FAUNE-PACA - ALTERECO_2017_12_18. 33 records from PROJET DE PARC EOLIEN DE L’HERBUE - Données Faune Flore du parc éolien de l'Herbue. 9894 records from Biofokus. 5553 records from Anymals+plants - Citizen Science Data. 1 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 13 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 17 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 28635 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 24 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 4 records from Planktic foraminifera abundance of Hole 14-140. 30 records from Total foraminifera counts from M35/1_MSN1043. 249 records from Collection Francaise de Bacteries Phytopathogenes. 4949 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 225 records from New Brunswick Museum Collection. 74 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 6 records from Policládidos de la Península de Yucatán. 498 records from Lichens of North-Eastern Poland. 160 records from artsprosjektet_53-12_enchytraeidae. 14296 records from Paleobiology Database. 12610 records from Ocean Salmon Program - Barkley Sound Juvenile Salmon Study from 1987 to 1994. 3 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 7 records from Parc éolien des Landes de Jugevent - Autre faune Brignac. 17 records from Cochlostoma revised: the subgenus Clessiniella Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 7 records from MIRC KB23 Shoreline Surveys May 2013. 23 records from Movimiento migratorio de la tortuga carey. Islas del PNSAV. Veracruz, Ver., México. (aggregated per 1-degree cell). 7 records from Plan de gestion 2014 - 2018 du site des Grottes de Sare (64) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 38 records from ColRest_Raw1. 405 records from database_fish_estuary_boso. 14 records from Plan de gestion 2009 - 2013 du site de la butte de Launay (33) mené par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 15 records from Planktic foraminifera abundance of Hole 74-525B. 23 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 3022 records from flora&fauna(NIBR)2019. 861 records from Distribución potencial de pargos en el Pacífico mexicano. 1319 records from Réserves Naturelles de France (RNF) - RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 26 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 181 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2012. 65 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 25518 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 1 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 104 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 41 records from Inventaire de la flore des Landes 2012-2019 - Inventaire de la flore des Landes 2017. 76 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LEDOUX Jean-Claude. 25 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 16 records from Données espèces - Expertise IPE 37. 3 records from Ditylenchus sarvarae sp. n. (Tylenchina: Anguinidae) from Iran. 27511 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 3 records from Crustacea ZMK. 10 records from Benthic foraminifera abundance of Hole 84-567A. 117 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 371 records from ICEL (Land - Invertebrates). 622 records from UTEP Herpetology (Arctos). 1877 records from Biological Reference Collections ICM-CSIC. 5 records from Review of Aphidiinae parasitoids (Hymenoptera: Braconidae) of the Middle East and North Africa: key to species and host associations. 30 records from Total foraminifera counts of multinet POS247/2_MSN1380. 60382 records from Maritimes 4VSW Research Vessel Surveys. 16619 records from AMNH Herpetology Collections. 723 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 3023 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 48 records from Birdrace-Hügelland-Mainz/Bingen. 560 records from SWFSC Marine Mammal Survey, STAR 1999, Cruise 1613. 2 records from Planktic foraminifera abundance of Hole 9-78. 64 records from Ichthyologie ZMK. 37 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 3 records from Mammals in MZNA-VERT: project Loza. 24 records from Plasm bearing foraminifera counts of multinet M26/1_MSN844. 29 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 5 records from Insect (KIDR-IN). 3 records from marine metagenome Metagenome. 1 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 3 records from Sea Education Association Sargasso Sea Cruise C247 May 2013. 156 records from Species lists for benthic communities of Norwegian fjords from environmental surveys (data used in Sen et al. Estuarine, Coastal and Shelf Science 2022). 11 records from Invertebrates (except insects), Outer Hebrides. 2 records from New species of Cirratulidae (Annelida, Polychaeta) from abyssal depths of the Clarion-Clipperton Fracture Zone, North Equatorial Pacific Ocean. 27 records from Mammalians Specimens of Akita Prefectural Museum. 6 records from Amphibia and Reptilia of Yunnan. 150 records from Los mamíferos del estado de Durango, México. 1 records from Shotgun metagenomic analysis of Lake Paajarvi sediment microbes.. 775 records from Observations opportunistes rassemblées par l'Observatoire PELAGIS - Observations opportunistes de mammifères marins de l'observatoire PELAGIS. 36 records from MSB Fish Collection (Arctos). 50860 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 43 records from Planktic foraminifera counts of sediment core V28-25. 29 records from Langes Tannen (Uetersen). 28 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par piège photographique) réalisées par le CEN Aquitaine. 135 records from Churchyards for London. 60 records from Biodiversity of the scentless plant bugs (Hemiptera: Rhopalidae) in southern South America. 37 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude d'impact projet cluster des médias Jeux Olympiques. 70 records from Sightings from R/V Song of the Whale during the spring 2019 MAPS survey (NMFS permit 14809). 535 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 5 records from Wairambar Rainforest Species list 2018. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste JOB Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 138 records from Campagnes d'observateurs embarqués sur navires de pêche : campagnes PETRACET/PROCET et OBSMAM - Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 5263 records from Transfert de fichier de données naturalistes d'observateurs indépendants à l'Observatoire FAUNA - Données naturalistes de Frédéric REVERS. 3 records from Happywhale - Rough-toothed Dolphin in South Atlantic Ocean. 16 records from Plan de gestion 2019 - 2023 du Lac de La Prade (33) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 283 records from North Carolina Aquarium at Pine Knoll Shores Sea Turtle Awareness (aggregated per 1-degree cell). 1046 records from Biodiversidad asociada a la modificación del Plan de Manejo Ambiental Integral de Mares. 557 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 9 records from Assistance technique à la gestion écologique des espaces naturels propriétés de ValOrizon sur la commune de Damazan (47) menée par le CEN Aquitaine entre 2017 et 2023 - Observations faunistiques (inventaire) réalisées par le CEN Nouvelle-Aquitaine. 5 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Mr MONTAGNER Sylvain. 30 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Guaminí (Carrique, octubre 1999). 6 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 2 records from Planktic foraminifera counts of sediment core V19-19. 6 records from Monitoreo de aves en la zona del Anchicaya (Colombia, Valle del Cauca, Buenaventura) en el marco del Convenio de Investigación Icesi/Celsia. 24 records from Total foraminifera counts of multinet POS247/2_MSN1388. 3 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 161 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données du partenariat Imerys - UMS PatriNat - 2018-2024. 15 records from Pempheris bexillon, a new species of sweeper (Teleostei: Pempheridae) from the Western Indian Ocean. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Mission ONF 2008 d'inventaire de la Réserve naturelle de la Trinité. 3 records from Birkenloh. 273 records from Species observations during citizen science expeditions. 22 records from demande d'autorisation d'exploiter une carrière alluvionnaire sur la Commune de Neuviller sur Moselle - Neuviller-sur-Moselle - Inventaires faune-flore 2013-2014. 2197 records from Coleção Entomológica Moure e Costa. 81 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Ruben JIMENEZ. 87 records from Ferme éolienne de La Chapelle Bâton - Données biodiversité - projet éolien La Chapelle Baton. 24 records from Polymetallic nodule field Targeted loci environmental. 23 records from NSG Karwendel. 18 records from Total foraminifera counts of multinet M12/3_MSN562. 58 records from (Table 1) Stratigraphic occurrence of selected diatom species from ODP Hole 105-647A. 4 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de DUNESME Caroline. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Hélène MALéJACQ. 357 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 48 records from Identification of Important Turtle Areas for green turtles in the Sulu Sulawesi Marine Ecoregion (aggregated per 1-degree cell). 131 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 211 records from Transmissions de données opportunistes du Parc Naturel Régional Périgord-Limousin (PNRPL). 5 records from Planktic foraminifera abundance of Hole 28-264A. 236 records from Réseau Loup - Lynx ONCFS - Réseau Loup-Lynx : Répartition communale Occasionnelle du Loup en 2015. 8191 records from Records of protected animals species in Ukraine. 3 records from Range table from planktonic foraminifers in ODP Hole 170-1043A. 82 records from annex3. 3 records from Lustbach-Umland. 2458 records from Ireland's BioBlitz. 311 records from AMAPPS Southeast Aerial Cruise Fall 2017. 317 records from Muscidae (Diptera) records from Britain and Ireland to 1985. 14 records from Eschlberg Thalhausen. 14 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 18 records from Plasm bearing foraminifera counts of multinet M12/3_MSN538. 28 records from Ecología invernal de Setophaga striata en Colombia. 160 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Beaumonts Nature en Ville provenant de la base de donnée du SINP Île-de-France CETTIA. 534 records from Ecology of Lahille's bottlenose dolphin Tursiops truncatus gephyreus in the Patos Lagoon estuary and adjacent marine coast. 306362 records from Garden Bird Surveys. 1 records from British spiders in the collections of World Museum, National Museums Liverpool. 819 records from Regroupement d'études et inventaires - Données opportunistes. 1 records from Planktic foraminifera abundance of Hole 9-80. 17 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 11 records from Trockenhang Greinhartsberg Edelfingen. 18 records from Locations at sea of adult females of southern elephant seals (Mirounga leonina) from Península Valdés, Chubut, Argentina. 86 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 1 records from Tag der Artenvielfalt BUND Kaiserslautern. 14 records from Swedish Malaise Trap Project (SMTP) - Coleoptera. 631 records from National Taiwan Museum. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Christophe HERVE. 19714 records from SER Species-based Surveys. 276 records from Historical landings from the Venice (Italy) fish market between 1905 and 1927. 3 records from River Macrophytes Database. 1176 records from NINA insect database. 1 records from Saisie de données naturalistes d'observateurs indépendants sur la plateforme de l'Observatoire FAUNA - Données naturalistes de Charlotte DUBREUIL. 36 records from Macromycetes in Portugal Update. 421 records from Fortalecimiento de la Colección de fotocolectas biológicas (CFB): una propuesta del uso de la imagen digital al servicio del conocimiento de la biodiversidad. 142 records from Cetacean Stranding Data in Hokkaido. 1764 records from SILENE-FAUNE-PACA - PNR_Alpilles_2017_12_18. 33 records from Projet d'extension de carrière et de mise en place d'une unité de concassage de produits minéraux - Pierrefonds - Saint-Pierre (974) - Inventaires des Oiseaux. 1190 records from Lichen herbarium TRH, NTNU University Museum. 21 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste DURAND Bruno provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from éducation à l'environnement - projet rapaces nocturnes - Inventaire rapaces nocturnes. 80 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 33 records from BIRDRACE TEAM BO-BACHTER. 5 records from Zitadelle Berlin-Spandau (7b). 1 records from Two new species of Neotrichoporoides Girault (Hymenoptera, Eulophidae) from China and a key to Chinese species. 11 records from Oberservation of birds at station PS14/159 along 49° West. 74 records from Collection entomologique Barthélémy. 1097 records from MMS Low Altitude Survey for Mammals, Southern California Bight 1975-1978. 3 records from Sandhofen. 214 records from ULg_Hexapoda. 1 records from New data on the genus Pycnoscelus Scudder, 1862 with the description of P. schwendingeri sp. nov. (Blaberidae: Pycnoscelinae). 223 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 88 records from ZFMK Orthopteroidea collection. 23 records from marine sediment metagenome Metagenome. 2 records from Données espèces - Expertise IPE 83. 1124 records from Colección de Tejidos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-CT). 326 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 3412 records from SPC PROCFish/C Fish Observations Solomon Islands 2006. 30 records from HSU Vertebrate Museum Reptile Collection. 1749 records from FWRI EPDC NonNeonate SeaTurtle Observations. 297 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 164 records from Planktic foraminifera abundance of Hole 26-258A. 61 records from Data from ILAM surveys conducted by ARCOS in Rusumo landscape for year 2017. 33 records from Inventaire du domaine d'Abbadia - Suivi Rhopalocères. 2 records from Plan de gestion 2016 - 2020 du site du vallon du Clamondé (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 46 records from Australian Sea Lion and New Zealand Fur Seal Distribution Database from Coastal and Marine Resources Information System (CAMRIS). 217 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure MNHN provenant de la base de donnée du SINP Île-de-France CETTIA. 73 records from Spain Tags merged (aggregated per 1-degree cell). 40 records from ONCFS Réseau Ours brun - Ours 2012 présence Régulière Mailles 10km LAEA Réseau Ours brun ONCFS. 4 records from Antarctic fish by-catch observation during krill fishing cruise onboard polish trawler Dalmor II (March to July 2011). 23 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 16538 records from Bird Observation Data. 2 records from marine methane seep Targeted Locus (Loci). 278 records from 2011 Female Northern Elephant Seals (aggregated per 1-degree cell). 642 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 11 records from Gulf of Maine Razorbill Tracking (aggregated per 1-degree cell). 65 records from MfN - Mallophaga Collection. 9 records from The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records. 310 records from Spider Mites Collection of Jean Gutierrez. 16 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 170 records from Gabon 2007-08: Mayumba, Leatherback Turtles (aggregated per 1-degree cell). 1709 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 1 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 188 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 32 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 25 records from Plan de gestion 2017 - 2021 de la Réserve Naturelle Régionale d'Errota Handia (64) mené par le CEN Nouvelle-Aquitaine - Observations d'oiseaux réalisées par le CEN Nouvelle-Aquitaine selon le protocole STOC EPS. 2 records from Planktic foraminifera counts of sediment core V28-122. 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 10 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 38 records from Données des membres de l'Association française d'Arachnologie. 4 records from Wildlife inventory on two CRIPADD NGO sites in the municipality of Kpomassè. 646 records from Amphibian and reptile data for Dumfries and Galloway.. 10 records from Étude de deux bras annexes de la Baïse (47) réalisée en 2016 et 2017 par le CEN Aquitaine - Observations faunistiques (inventaire) réalisées par le CEN Aquitaine. 779 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 2 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 297 records from SILENE-FAUNE-PACA - OPIE_National_2017_12_18. 4481 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 10 records from Survey of Eurasian otter distribution in the Glenmore - Aviemore area, 2018: Camera trap mammal records. 8649 records from CAS Herpetology (HERP). 2 records from Área ocupada por especies de fauna en el Parque Nacional Natural Selva de Florencia en el 2018. 13 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 20 records from Two Hexapleomera species from Japan, with a new species description and discussion of phylogenetic relationships within Hexapleomera (Crustacea: Tanaidacea). 24815 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 41 records from UNCW Aerial Surveys for monitoring of proposed Onslow Bay USWTR site - Right side -. 7 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Reptiles). 68 records from Vertebrados terrestres de San Juan de Camarones, Durango. 6 records from The Indigo Project: a global citizen science Ocean survey. 569 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 4504 records from HSU Wildlife Birds. 222 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 883 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 951 records from Odonata Central. 3672 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: complementary work sites [2010-2014]. 3878 records from Mammalogy Collection - Royal Ontario Museum. 4635 records from Tern Island Albatrosses - 1999. 20 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 30 records from Total foraminifera counts of multinet POS231/3_MSN1335. 86 records from Registros de fauna en el bosque seco tropical en la zona de amortiguación del Parque Nacional Natural Tayrona, Santa Marta, Colombia. 986 records from Seasearch Marine Surveys in the Isle of Man. 216 records from Levantamientos portuarios de fitoplancton, zooplancton, perifiton y macrozoobentos en el Pacífico colombiano. 8 records from CBCGDF CCAfa Volunteer Observation Archive. 29 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 11 records from Parascolopsis akatamae, a new species of dwarf monocle bream (Perciformes Nemipteridae) from the Indo-West Pacific, with redescription of closely related species P. eriomma. 4 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 12 records from Planktic foraminifera counts of sediment core RC11-147. 24 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 18 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 2 records from Plateforme AUVERGNE-DREAL Auvergne - Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 8 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes d'Emmanuel SECHET. 24 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1337. 128 records from HRC CRC Small Vessel-Based Monitoring Surveys March-April 2006. 2 records from North Pacific Subtropical Gyre Microbial Community. 28 records from Bryophytes, fungi and lichens on dead wood. 13 records from (UTCR) University of Tennessee - Reptiles Collection. 3 records from Artensuche auf den Elbwiesen in Radebeul. 9 records from Hawksbill turtle tracking at Lighthouse Reef Atoll, Western Caribbean - MarAlliance (aggregated per 1-degree cell). 98658 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 135 records from NZCS Brownsberg Nature Park Camera trap Monitoring 2013-2015. 18 records from Inventaire en continu de la ZNIEFF 'Plateau de Saint Michel' - 720012960 - Plateau de Saint Michel - Inventaires Oiseaux IPA. 21 records from Naturschutzgebiet Lüneburger Heide. 4 records from Four new genera of the Ceratonotus group (Copepoda, Harpacticoida), including the description of two new species. 162 records from Учет следов по первому снегу (Белая тропа). 776 records from UAZ Mammals. 723 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LAGARDE Mathieu. 10 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 242 records from López-Uribe Lab Collection. 1 records from Gunma Museum of Natural History, Invertebrate fossil Specimen. 2 records from Plan de gestion 2015 - 2020 du site du site des zones humides du Mondarrain et de l'Artzamendi (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Aquitaine. 35 records from Réseau National Echouages de mammifères marins - Données Réseau National d’Échouages de Saint-Pierre et Miquelon. 6 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, 63-150 µm. 3214520 records from Southern African Bird Atlas Project 2. 69 records from Bird specimens of Obihiro Centennial City Museum. 56 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 2251 records from Seasearch Marine Surveys in the Channel Islands. 22 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude d'impact de la ZAC Bellevue - compléments. 25 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 71 records from Fish Specimens. 34 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 13 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 6 records from Abundance of benthos infauna at station GIK23006-3. 97 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 280 records from NMBE - Arachnological collection. 9 records from Northern elephant seals post-breeding 2015 MALES (aggregated per 1-degree cell). 62 records from VIC - Herbário da Universidade Federal de Viçosa. 2 records from Southern Ocean microorganisms Targeted Locus (Loci). 2 records from Données opportunistes ponctuelles portées à connaissance de l'Observatoire FAUNA. 6 records from Planktic foraminifera abundance of Hole 23-229. 1179 records from Arctic Ocean Diversity. 29082 records from Catch data from New Zealand research trawls since 2008. 18 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de Jean-Michel LEMAIRE. 3 records from Occurrence of mammalia relicts at site Dolni Vestonice. 1017 records from Suivi des oiseaux de passage : programme ACT - Programme ACT : Répartition Alouette lulu 2007 - 2011 Coordonnées GPS Lambert 93. 3 records from Amplicon-Based Illumina Sequencing Reveals High Diversity of Phytoplankton in the Coastal Waters of Qinhuangdao. 15 records from Ulster Wildlife Living Seas Marine Species Records. 24 records from Total foraminifera counts of multinet FCA97C_MSN1343. 1 records from Parc éolien d'Argillières - Entomofaune. 27 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 297 records from Invasive Alien Species in Denmark. 6 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Planktic foraminifera abundance of Hole 39-354. 8 records from Revision of some types of North American aleocharines (Coleoptera: Staphylinidae: Aleocharinae), with synonymic notes. 10 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 1658 records from Collection Herpetology SMF. 2 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Murciélagos). 3 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 18 records from (Table 1) Planktonic foraminiferal abundance at DSDP Site 94-606. 1701 records from Waarneming.nl (NL) - Great Grey Shrike Count 2012-2013. 1 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données naturalistes de PICHARD Olivier. 178 records from Corn bunting surveys on the Western Isles. 761 records from Archives of the Arctic Seas Zooplankton. 12215 records from The Fish Collection. 21 records from Plot-based observations of macrofungi in raised bogs in Western Siberia (2014-2021). 248 records from Invasive Non-Native Species. 38 records from Avon Baselining - Waterbirds. 12 records from Pelagic Microbiome: viruses to protists. 16S and 18S data from oceanic samples collected at the chlorophyll maximum.. 20 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 1 records from estuary metagenome Raw sequence reads. 2 records from Herbier de Strasbourg. 31 records from (Table 7) Planktonic foraminifer abundance of ODP Hole 162-983A. 5 records from Planktic foraminifera of sediment core GeoB1406-4. 8 records from Naturschutzstation Schmidsfelden. 1 records from BB-Biodiversität b. 12 records from Renouvellement et extension carrière de calcaire les Devèzes - Données carrière Crayssac - Espère. 43 records from Birdrace-Thüringer_Becken-Sömmerda. 36 records from Database of the European mink (Mustela lutreola L., 1761) on Kunashir Island. 2541 records from Manitoba Museum of Man and Nature. 2 records from Coral. 6331 records from KUBI Mammalogy Collection. 437 records from Réserves Naturelles de France (RNF) - RNF - Données du Parc Naturel Régional de la Forêt d'Orient. 3 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 34 records from 1st Austrian Birdrace (Wien). 4 records from Rethymno Nesting Turtle (aggregated per 1-degree cell). 38 records from BIRDRACE HGON Kelkheim-Rumpfteam. 3 records from Plan de gestion 2019 - 2023 de la Réserve Naturelle Régionale de l’Étang de Chourroumillas (64) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques (suivi par dénombrement) réalisées par le CEN Aquitaine. 154 records from Suivi Temporel des Oiseaux Communs - Inventaire indépendant de FrédérIc Revers. 247 records from Structure and function of contemporary food webs on Arctic shelves: A panarctic comparison. The pelagic system of the Kara Sea- communities and components of carbon flow. 237 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 1 records from Homoptera, Fulgoroidea and Jassoidea of Guam. 2184 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 24 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Stercorariidae. 22 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 285 records from Presencia de ciguatoxinas en la especie invasora pez león (Pterois volitans) y en otros peces arrecifales en dos áreas naturales protegidas de Quintana Roo: Arrecife de Puerto Morelos e Isla Contoy. 6835 records from Skandobs. 33 records from Walldorf-Wiesloch: "Natur über den Gleisen". 2 records from Annelida collection of National Museum of Nature and Science. 181 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 15 records from mabik_fu. 2 records from Suivi écologique 2018 sur le canal de Miribel et de la parcelle du Rizan suite à une opération forestière (année n+2) - Chiroptères. 27 records from Benthic foraminifera abundance of Hole 84-570. 53 records from GEO Biodiversity Day. 6 records from University of Nebraska State Museum Fish Collection. 66 records from Colección de Zoología Invertebrados - Helmintología. 23 records from IASTracker. Invasive Alien Species database. 3 records from A new genus and species of sand-hopper, Mauritiorchestia fayetta gen. nov., sp. nov (Amphipoda, Talitridae) from Mauritius. 325 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 27267 records from Ornitho.eus. 32 records from Planktic foraminifera assemblage in sediment core SU90-I06. 1 records from The Bergius Herbarium. 95 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 24 records from Total foraminifera counts of multinet POS247/2_MSN1384. 810 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 9 records from Planktic foraminifera counts of sediment core V16-20. 3 records from Naturpark Kottenforst-Ville 19.6.09. 1 records from Happywhale - Sei Whale in Southern Ocean. 43 records from Marine Water Column Samples Targeted loci environmental. 76 records from Transmissions de données opportunistes du Parc Naturel Régional Périgord-Limousin (PNRPL). 36 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 18 records from renaturierter Main (Kemmern bei Bamberg). 254 records from The Magoshichi Suda Insect Collection, The University Museum, The University of Tokyo. Coleoptera I (Scarabaeidae). 52 records from Geochemistry and sedimentology on core POS200/10_28-1. 24 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 128 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données de la structure Agence des Espaces Verts provenant de la base de donnée du SINP Île-de-France CETTIA. 38 records from Projet de mise aux normes des rejets d'eaux pluviales de l'Aéroport Biarritz Pays Basque - Faune flore. 1142 records from SILENE-FAUNE-PACA - Parc_Naturel_Régional_du_Queyras_2017_12_18. 29925 records from Reef Life Survey - Survey Records. 6910 records from North Marine Region sea snake collection records (DEW collation), Australia (1877-2007). 142 records from Herbarium of University of Coimbra (COI ). 203 records from Landesmuseum Kärnten. 6 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 128 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 3174 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 89 records from ioj_hemiptera_collection. 275 records from Oology (Luomus). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 5 records from Happywhale - Pantropical Spotted Dolphin in South Atlantic Ocean. 9 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Expertise habitat et Flore d'ENS de Seine-et-Marne en 2017. 18 records from Xstrata, GHD and DERM central Queensland flatback turtle monitoring (aggregated per 1-degree cell). 203 records from Bay of Fundy Species List. 112 records from Reptilia Collection of Museum and Institute of Zoology PAS. 12 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Marmet Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 21 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste mameli loriane provenant de la base de donnée du SINP Île-de-France CETTIA. 57 records from DUML surveys for the stock discrimination of bottlenose dolphins along the Outer Banks of North Carolina 2011-2012. 13 records from Taxonomic revision of the recent marine Corbulidae (Mollusca, Bivalvia) from Brazil. 1 records from Planktic foraminifera abundance of Hole 14-136. 257 records from UPCB - Herbário do Departamento de Botânica. 32 records from Amphibians and Reptiles census in the Western Siberia (2002 - 2009 years of research). 5 records from Monitoreo de aves en el Refugio de Vida Silvestre Pambilar. 5 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de LARCHEVEQUE Nelly. 6 records from Coleção Entomológica Ana Leuch Lozovei. 17 records from Hormigas (Hymenoptera: Formicidae) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 93 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 111 records from Cryptobiont assemblages's dataset of coral reefs using ARMS in B10 Reef and Mahahual Reef of the Great Caribbean. 2392 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Department of Plant Protection. 139 records from Herbarium BSG Lichenes. 23 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 11 records from IRAD Cameroon insect collection. 63 records from Données chiroptères. 104 records from Gestion de sites - Données invertébrés sites CEN MP. 92 records from Occurrence of bird species along Loduare - Golini Road, Ngorongoro Conservation Area, Arusha, Tanzania. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Etude des coléoptères de l'ENS de Voulangis (77). 1632 records from SILENE-FAUNE-PACA - Grand_Site_Sainte-Victoire_2017_12_18. 2 records from MfN - Fossil vertebrates V. 132 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 2393 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 3 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Observations issues des réseaux sociaux. 6 records from Mollusc specimens of Parthenon Tama History Museum (PTHM). 20 records from Total foraminifera counts of multinet M21/2_MSN644. 15 records from Numérisation des données faune contenues dans les Bulletins de la Société Linnéenne de Bordeaux - Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 9 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 223 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 5 records from Ostracoda abundance of Hole 95-612. 35 records from RIVM (NL) - Earthworm Observations in Soil Samples. 6 records from FERME ÉOLIENNE DE BLANZAY - autre faune Blanzay 2016. 66 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 5 records from Projet éolien en mer de Dieppe Le Tréport - Mammifères marins - transects en mer-Avion. 151578 records from AMNH Bird Collection. 582 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 798 records from Inventaires naturalistes et gestion des espaces naturels du foncier privé d'EDF - Données CEN M-P - EDF. 462 records from 台灣真菌地理分布系統資料庫之建制與應用(1/4). 17 records from IMMS Ridley 1 (aggregated per 1-degree cell). 79 records from BioBlitz Barcelona 2010-14. 9 records from Plan de gestion 2015 - 2022 du site de Castelmerle (47) mené par le CEN Nouvelle-Aquitaine - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 23 records from FFH-Gebiet "Calwer Heckengäu". 2 records from CardObs : Observations naturalistes issues de l'outil de saisie et gestion CardObs mis en place par le Service du Patrimoine Naturel (MNHN) / UMS PatriNat (OFB - CNRS - MNHN) - Données arachnologiques de contributeurs étrangers. 386 records from Birds - Wild Birds (KIDR-BI). 38 records from Planktic foraminifera counts of sediment core V25-56. 11474 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 36 records from Bob Merritt Coleoptera Dataset. 10 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 12 records from Happywhale - Indian humpback dolphin in Indian Ocean. 1 records from MIRC PIFSC Small Vessel Surveys Feb-Mar 2010. 54 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 2605 records from Données LPO Réserves Naturelles Nationales - Données LPO Réserve naturelle régionale du marais de la Vacherie. 76 records from USWTR Onslow Bay Aerial Survey -Right side- 2010-2011. 2 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 3 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 184 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 15883 records from Canadian Lakes Loon Survey. 47 records from Alan Wormington Collection. 653 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 84 records from University of Saskatchewan. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 6 records from Relative abundances of benthic foraminifera in surface sediments (Table A3). 1 records from Occurrence of mammalia relicts at site Rotselaar. 21 records from CorMedNet- Distribution and demographic data of habitat-forming invertebrate species from Mediterranean coralligenous assemblages between 1882 and 2019.. 22 records from SMDB - Santa Maria Departamento de Biologia. 72 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 6 records from Assistance technique à la gestion écologique des espaces naturels propriétés de ValOrizon sur la commune de Damazan (47) menée par le CEN Aquitaine entre 2017 et 2023 - Observations faunistiques fortuites réalisées par le CEN Nouvelle-Aquitaine. 291 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 5 records from Système d'Information sur la Nature et les Paysages d'Ile de France - Données du naturaliste Matthieu Gouirand. 30 records from Birdrace-Die_Paradiesvögel-Herford. 29 records from Plathelminthes - SMF. 169 records from Insect specimens of Rikuzen-Takata City Museum. 20 records from Extension Carrière de la Jaunaie - Données biologiques Carrière La Jaunais. 1 records from Foraminifera abundance of Hole 60-459. 7 records from Planktic foraminifera abundance of Hole 26-255. 1505 records from Cowan Tetrapod Collection - Mammals. 5 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 21 records from Données espèces - Expertise IQE 306. 55 records from Données de l'association Nature 18 - Données Nature 18 - Études faune 2016. 1863 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 12 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 39 records from VACAPES Vessel Nearshore Humpback Whale Monitoring 2015-2019. 79 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 703 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 9 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 2856 records from LSUMZ (LSU MNS) Fishes Collection. 1 records from 2. Donauinsel bei Entau. 2 records from Happywhale - False Killer Whale in South Atlantic Ocean. 35 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 469 records from Ornithologie Federsammlung - SNSD. 323 records from LISU Lichen collection. 3 records from Liether Park (LMS), 5a. 3 records from JAX MISSILEX Aerial Monitoring 2010. 13 records from Herbarium (ICEL). 855 records from Réserves Naturelles de France (RNF) - RNF - Données de la Communauté de Communes de Gevrey Chambertin. 150 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 18 records from bmhs_moth_collection. 870 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 521 records from La Planète revisitée - Corse 2019-2022 - La Planète Revisitée Corse 2020 : prospections Agriate, Saint-Florent et Cap Corse. 265 records from SEFSC GoMex Oceanic 1993 (W). 6579 records from WCPS Bird Survey Project. 43 records from Sylter Meerstrandläufer. 216 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Peces. 108 records from DFO Zoobenthos data from upper Frobisher Bay, 1967 to 1973. 2780 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 33 records from NEON Biorepository Carabid Collection (DNA Extracts). 28 records from Total foraminifera counts of multinet M10/2_MSN218. 18 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 4 records from UAM Herbarium (ALA),
Keywords: GBIF; biodiversity; species occurrences